PERANAN SKRIPSI DALAM PENCAPAIAN TUJUAN PENDIDIKAN BAHASA - -, G Suharto (Diksi, 2015)
<img src="data:image/png;base64,iVBORw0KGgoAAAANSUhEUgAAAVAAAAGnCAIAAABuHZgvAAAgAElEQVR4nOy9Z1gUS/r/PR49KoJEyUmikjGgCCoKohgwIkgQFSUnRUGBAUFyUHKQDJIFBAmSo4jkIEmCwhBmGMLMEGYYwvTzop6di8uzv939755Mf154SU13dVV1f7sr3PddCAgGBmbTgPijCwADA/P7AQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYTAQseBmYT8acWPIVCWV5eXlxcXFpaWlpaIpFI1J9WVlZAIpFIpP5KoVBWV1dBCpFIBP9ZXV3dmOfa2hqRSCSTyRQKBaSAU1ZWVsAV19fXl5eXiUTi6uoq9Zjl5eWNWVEoFBKJND8/TyaTqdmSSCQikbi2tvZDLYhE4szMDBaLxePx4CogEY/HgzKD/GdnZ2dnZ0F9Z2dn5+bmQAoejwfXXVtbIxAICwsLa2trq6urBAKBeszi4iK1qOvr6/Pz8xgMZnJycnZ2llqvhYWFhYWFlZUV6pFra2tLS0vUTHA43PLy8sbGB+1MIBAWFxfX1tYoFAqFQiGTyXg8fmlpaX19/Yearq+vE4lEHA5HbRYKhQJqSm0r0HQ4HA6PxxOJRGom4L7g8fiZmZmZmZm5uTlqpchk8sbKzszM4PF4MpkM0peWlqjXWlxcBK1KvWvT09Pj4+Pj4+NYLJZaKsDS0hIWi11YWNh4OgaDAU2HwWA23q+1tTU8Ho/FYkHFKRTK2tra/Pz89PT00tISKCfIYXp6mlpyCoWytLQ0PT09Pz8PUtbX1+fm5mZmZjY29e/Jn1rwy8vL79+/DwwMDAkJCQoKiomJaW1tJZPJ6+vrnZ2dUVFRQUFBISEhwcHBoaGhubm5BAKht7c3NjYWJAYHB4eFhVVXVy8uLlLz7OnpiYmJyc3NxeFwIGVoaCguLq64uBik4PH4kpKSlJSUgYEBcMDCwkJOTk5oaGhrays1n5KSEi8vrw8fPgCFo9Ho7Ozs1NRUNBq9sQpTU1NxcXFGRkY6OjpPnz4tLCwED+j79+8dHR0rKiqWl5dJJFJWVtbjx4/DwsL6+/uTk5NNTU0fPnxobW1tZWWFRCKrq6shCBobG/Py8goNDcVisaOjoy4uLhYWFuCYV69edXZ2gvdCb2+vh4fH9evXL1++bGlpWVxcvL6+vri4GBcX9/Lly46ODmrZZmZm0tLSLC0traysrK2tbWxs0tLSsFgs9QASiVRVVYVEIkNDQ0dHRyEIWl1dbWxsfP78eXp6OoFA+OF+TU9PJyYm2traVlZWUnPIzc199uzZixcvPn36BBLz8/MfPXpkb2+fk5MzPz8PEgkEQnFxMRKJNDAwMDIyevToUVBQUF9fHwRBbW1trq6ujx49sra2fvjwobGxsb+/f3d3d3d3t6+vb0REBLXNExMTXVxcGhoaIAhaWlpKT0+/d++eiorKyZMntbW1s7KyqGWmUCjx8fFaWlrh4eHUl87bt2/V1NQuXLhw8eJFDQ0Ne3v7mpoa8NO3b9+eP39+8+bNxMRE8DjNzc1FRUXdvn07NzcX3NPp6enIyMhbt25FRERMT0+DB7igoMDAwMDd3X1sbAw8S/b29qamps3Nzf/m6f9t+FMLnkAg3Lx5k5eXl52dnYGBgZOTU1FRsaCggEAgvH79WkJCgoODg5mZmZGRkYmJ6cqVK9+/f09JSZGQkODi4mJiYmJkZOTk5FRVVU1PTwevaiwW6+bmJiIicvTo0a6uLnCVvLw8SUlJOTm50tJSCIJQKJS1tbWysnJ+fj44oLm5WVVVVUBAwN7envr18PHx4ebmvnz58uDgIARBDQ0N6urqZ8+ebWtro5Z/cnLSyclp//79rKys7Ozsu3fvPnbsWFVVFYlEQiKRfHx8L1++JJFIBQUFMjIyR44cKSoqmpmZMTU1paWl5eHhERYW3rt37549e65evVpZWVlfX3/06FFVVdWBgYHm5mYBAQEaGhoBAQEeHh52dvabN2/29vYODw9bW1vz8vLy8/NLSEiws7OfOHGiuLgYjUbfuXNHXFw8NjaWWrzR0VEzMzM6OjouLi4+Pr7du3cLCws7ODhQVdHe3q6np8fCwiIqKlpWVgZBEJFITEhIEBUVNTExAU/wRj5+/CguLs7IyGhjYwN+xePxjx494uDg4OTkdHFxAYeZm5szMjJyc3Pb2NhMTU2BxJmZmYCAACEhIRoaGj4+Pi4uLl5eXmNjYxQKlZubKyIismfPnr179+7bt4+dnf3GjRt1dXUlJSUnTpwQEhJ6/fo1yERbW1tCQqKgoGBxcTE2NlZSUpKVlVVaWlpQUHDHjh0SEhKpqangyKGhoUuXLm3ZskVVVfXbt28g0dXVFYFAsLGxHTp0SFhYmIGBQV9fH7xNUlNThYWFEQiEmpoaKPP4+LiJiQkLC4ufnx9osdbWVnl5eQQCoaCgUFVVBZorICCAi4uLk5MzIiICgqCpqaljx44JCQnl5ub+t7L4n/hTCx6HwykrK2/fvl1RUdHMzExdXX3Lli26uroNDQ1OTk7bt28/cOCAubm5vb29nZ0deK26u7tv3bp13759FhYWNjY2x48fRyAQ6urq4EtSW1t78uRJBAKBQCASExOBehMTE0GKpaXl7Ozst2/f1NXVOTk5U1JSIAgiEAi+vr709PQIBOL06dPt7e2gbM+ePUMgENu3b3d1dV1YWGhtbZWVld27d299fT21/M3NzUJCQggEwtjYOD4+XkdHR1hY+OXLl+CdQk9Pj0Qis7KylJWVGRgYnj9/Drp5mpqaO3bs0NfXj4yMjIiIOHbsGD09/bNnzwoKCkRERGRlZXt6empqamhpaUVERJycnHx9fY8ePcrAwBAVFRUTE8PHx8fExOTp6VlUVHT37l1hYWFfX18UCnX9+vVt27Z5eHhQizc6Onrr1q0dO3bo6Oh4eno+fPiQh4eHk5MzNzcXlCQ9PZ2bmxs0jre3N4lEWlpaCg0NZWJi0tLSouoEQCQSg4ODwcFKSkpFRUXgDt6+fRskqqurE4nEubk5FRUVBAKxbdu2e/fuTU5OgtNnZmY8PT3p6ekVFRWDgoKePXsmLCy8Z8+eioqKrKwsOjo6QUFBb2/vxMTEyMjI9+/fj4yM5OfnS0pKgvsyMjKytrZ2/vx5FhaW7Ozsr1+/glY1NjbOyclJTk6+evUqAoG4cuXK4uLi6upqWlravn37EAiEuLh4amoq+B7Y29tv27ZNX18/JycnJiZGVFSUm5s7Pz9/eXnZxsaGkZFx586d3NzcoKsyPj5uaGjIxMTk5+cHnq6MjAw6OjoGBgZmZuaAgADQJv7+/lxcXAgEArxZBgcHjxw5IigoCAv+n4DD4TQ0NAQEBLKysiAI6ujoEBUVlZWVTUhIcHFx2bNnj4GBQWNj4/Dw8OjoKOhoPX/+nIWFxcjICIy1vL29t23bJicnB7rrvr6+oqKiPDw83NzcRkZGoNOekpJCS0u7bdu2ffv2vX37dnBw8PLly/z8/BkZGRAEdXd3q6mpiYqK8vHxycnJBQcHg7I9fvz4559//vnnn2VkZGpra7u7u1VVVffv3w/6k4CmpiYBAYGtW7c6Ojq2tbUVFhZ6eHjk5+ePjY3Z2toyMTFdunRJQUGBh4fn4cOH4+PjEAStr6/fuHGDhYUlPDx8ZmZmYmLi7t27zMzMjo6O1dXVUlJScnJyvb291dXVbGxsOjo6GAwGgiAPDw8WFhZbW9tXr14JCQmxsLD4+vq2tbWlpqa+ePGipqZmYmLixo0bDAwM/v7+1OKNjo7evHmTj4/v3bt3IMXW1paOjs7MzAx07D08PNjZ2ZWUlNjZ2TU1Nfv6+shkcmRkJDs7u56e3vfv3zferC9fvujp6bGysp4+ffrAgQNeXl4QBOHxeH19fVpa2p9++klZWbm/v7++vv706dM///wzExOTkZERtTeOxWJdXFyYmZlBR2BiYkJLS2v79u3Z2dm5ublMTEwHDhzIzc1taWlpaGgYHh5eXV0tKSmRlZX9+eef+fn53dzccDicjo4OMzNzeHh4Xl7e3r17VVVVqf24pqYmPT29Z8+e4XC4mZkZMzMzWVnZo0ePHj9+3NTUFPTAnz17RkdH5+PjA6YSbty4wczMHBYW9uXLl3PnzikqKt66dYuTk9PT03N+fn5qasrQ0HDPnj0vX75cWFhYXFx0cHDg4eGxsLDYv3+/vr7+wsLC0tJSYGAgLy/vzp07RUVF3dzcPn/+rKSktH///oKCgl9XLP8hf2rBg68BGxtbQEAACoWKjY3l4OBQVlbOzc318PBgZGQUFha+fv26pqammZlZSUnJ6uqqp6cnAwPD8ePHAwMDg4ODz507t2fPHhMTEzBRd+XKFSkpKW9v71u3bsnLy+fl5UEQlJyczMzMLCIiwsrKevv27YKCgqtXr4qIiGRmZkIQlJWVxc/Pb2Rk5OHhAYaC4M1iY2PDwcEhKyt7+PBhBweHuLi4U6dOiYmJbRT86Oioubk5Ly8vCwuLlJTUnTt3EhISJicniUSivb09AoHYsmXLzz//fPLkSertJ5PJN2/eRCAQ586de/LkiYGBARsbm7i4eGFh4cDAgKys7KFDh3p7e2tra1lYWBQVFd+8efPu3Tt1dXVWVlY/P7/W1tanT59ycXGxsLAcOnRIW1s7Li4Oj8djMJirV6/y8/NHRUVtLB4YMWVmZoIppfj4eF5e3uvXr4+OjoInHrxe9fT05OTkUlNTV1dXX79+/U8Fn5qaKi0tfe3atbi4OKANMpk8Ozuro6PDxsbGycl5/fr1lJSU0NBQTU1NPj4+Dg4OIyMj6hd+amrq+fPnzMzMOjo65eXlERERUlJSrKysZWVlubm5jIyM27dvl5GROX78uLS0tLOzM5FIrKysFBcXFxMTU1FROXz4cGVlJXhXurq6vnz5kpub28DAALxGAWBGFoKgrq4uWVnZK1euREdH6+npycvLf/nyBYIgJyenbdu2Xbt2LSAgwMfHR1xc/ODBg9nZ2XFxcYKCgjY2Nu/fv5eWllZVVe3s7Jydnb13796ePXtevXq1tLRUW1urrKysqqra0NBw8+ZNKSmp8vLyxcXF4OBgDg6OgwcPXrhw4ciRI7GxsQoKCmJiYtQB4+/Mn1rwOBxOSUlp69atXFxcYmJiPDw8tLS07u7u3759c3d3p6en5+PjO3v27OXLl42NjfPz88lkso+Pz65du2hoaNjY2FhZWWloaKSkpDIyMshk8qdPn8TFxc+cOfPp0yd3d3dOTk5vb28IgjIzMzk4OK5du6atra2srKytrX3p0iUpKamcnJylpSU7OztWVtbQ0NCuri4NDQ0xMbHPnz9DEIREIoWFhe/fv+/g4KCoqHju3DkJCQkJCQnwK2BlZWV4eDguLs7Q0FBOTo6ZmVlCQiIoKOjbt2/Ozs4IBGLnzp3s7OxsbGwPHz4EH1UKhaKnp4dAIDg4OGRkZEC3U01NDYVCjY6OysjIAMF/+vSJkZGRhoaGh4eHl5eXiYnp3LlzHR0dZDL5+/fvSUlJRkZGioqKHBwcYmJir1+/Hhsb09TU3L9//5s3bzY2r4GBAQ8PT3p6Oph6TE9PFxISunTp0rdv34qKikRFRU+dOlVRUeHl5cXHx2dvb7+0tBQVFcXOzn779m0wjUfFxcWFk5PT1dW1trb23Llz0tLSNTU1GAxGW1ubi4vr1KlThoaGd+/evXbtmqWl5fHjx3ft2vXgwQPqFx6Hw4WEhIDJmr1793Jycu7evVtLS2tkZCQjI4ORkZGFhUVLS8vS0tLQ0DAtLW15ebmsrExERERLSysiIkJeXl5XV1dISGjv3r3u7u5+fn5cXFwPHjzYKHjA8vJyamoqBweHvr5+cXHx3bt3ubm5QW/Ow8MDgUDQ0dGxsbHx8vKCb/LAwICtrS3oNiYnJysqKrKysmZnZ+NwOENDQzY2tpCQEBKJFBAQwMrKev369YyMDC0tLRYWFjc3NwKBEBISwsLCYmBgEBYWJiMjc+HCBXZ2dmlpabhL/0/A4XAqKipbtmyRkZHR0dGxsrIKDg4eGRnB4XBOTk5MTEx37twpLy9vb2/v7++fm5ujUCiurq4sLCxnz54NCwsLDg6Wl5fn5OR89eoVDofz9vamo6NjZmY+ffq0mJgYAoHQ09MbHBxMSUnh5OQ0NzevqamxsrKioaHh5OQUFhYuKSkZGBgAA05paelz585xcHDQ0NA4OTnh8XgPDw8BAYEXL160tbVdvnyZjo6OlpZWSkqqsbGRWv4vX774+/vHxcV1dXW1trY6OTnR0tIqKytXVVU5Ozvv2rVLS0srNDT0yJEjzMzMbm5u4CxtbW1GRkYrK6vc3Nzc3NyjR4/u27evqqoKhUIdPHgQCP7jx4/MzMzCwsKGhobOzs7+/v6NjY2rq6vV1dUuLi5xcXHj4+Pt7e3W1tZbtmwBAtbV1RUXFwcTEwACgfDgwYONXfrg4GDQFOPj446Ojlu3bqWjo5OTkxMVFUUgENra2uPj43l5efz8/Hfu3KHOt0EQhEKhdHR0EAiEiIiIvLw8PT39jh07vLy80Gi0gYEBNzf3vXv3nj59KiAgwM7O7ufn9+DBgy1bthgYGFAFPzMz4+Pjs2fPHkVFxcePH7u7uyclJYGlh+joaG5u7mvXrrW0tKDRaDQaTSQSIQj68OGDkJCQvr7+4OCgv78/Dw/PTz/9dODAgaSkpJycHH5+fiUlJeqcS3d3t6OjY1JSUnd3t5GR0datW1lYWGRlZVlYWLZv3+7g4LC4uOjp6bljx44rV64EBQUlJiYWFhaOjY19+/btxIkTCASCnp5eUFBw586dCATC19d3YmICdKYiIyNRKJSZmRk4Zu/evXR0dKC5UChUcHAwMzOzmZlZd3e3nZ0dCwvLli1bFBQUPnz48FtK5//kTy34ubm5EydO7Ny509XVdXR0dG5uDqRPT087ODgwMDAYGBh8+vRpYGCgp6enr6+PRCI5OztzcHAgkUhwJBKJ3LFjh7a2dkdHx6VLl2hpaWVlZRUVFY8dO8bLyyshIRETE5OYmMjGxmZqakogEAoLCzk4OBAIBDMzc2lpaXZ2Nisrq6CgoJKS0qlTp2RlZRkZGWVlZTs6OsD41tXVFSz/8PDwIBCI/fv3bxR8VVWVpKSkhISEn59fRUWFs7MzDQ2NqqpqTU2Nra3trl27XF1dZ2dnExIS9uzZw8nJ+eHDBxKJBL4Pb9++BZncunULgUD4+Pi0traKi4tLS0v39PRUVlbS09NfvHixs7Nz43r427dvxcXFhYWFo6KiysvLTU1Nt27dCibYbt68KSgomJiYSD14dHRUU1OTlpbWxsYmIyMjPDz8wIEDwsLCubm57e3tioqKTExM6urq165du3Hjhri4uJycXFJSEhC8nJxcVFRUbm5uQUHBp0+fgoKCDh8+LCYmpqWlpaGhcfHixT179ly4cOHz58/37t1jZ2d3dHQMCQkBs3fp6em+vr7ghTsxMQEKMzs76+bmtnv37qdPn/6w4BcWFsbGxqaiopKWllZZWVlcXFxTU9PX15ednc3Pzw/m4QYHBxUVFcEkXH5+/tDQ0PXr1xkZGTU1NcPDw/39/S9evLh79+7nz5/n5eXt27dPVlb27t27hoaGWlpakpKSR48ebW9vd3V13bZt28ZpDgqFkpSUtHv37hMnTlhaWpqYmNy7d4+Tk/P8+fPFxcWurq579uzx9/dPSUk5cOAAJyeniYmJiYmJpaWlpKTk3r17IyMjXVxc6Onpb926NT8/39LScuDAAfD9AMPJ358/teBnZ2dPnjzJycmZlJS0MX1mZubFixd0dHTCwsIaGho6Ojrq6urGxsYjIyM+Pj78/PyOjo7AyiIiIgJMOyUlJUlLS6uoqLx//769vb2+vt7W1paTk9PMzCwxMZGTk9PY2HhqagqDwTg4OLCwsICZwhcvXrCxsXl4eHR0dHz9+jUrK0tdXV1AQCAjI8PFxUVCQsLd3X15eZlAIDx8+JCFheXIkSMtLS3Uco6Pjz9+/FhQUFBYWFhRUVFKSuro0aOgg41EIrm5ub28vObn53E4nJ2dHRgYDw8PGxsbCwsLg04mBEHm5uYcHBxeXl4NDQ3Hjh1TVlb++vVrXV2dsLCwiYnJD/1qFAqFRCKFhISkpaXPnj0rLS196tSprKysycnJO3fuHDlyhJotONjU1JSBgUFGRkZVVVVKSkpISAiJRGIwmLdv30pLS4MeEJjlCg4OVlJSsrKySk9Pl5WVZWVlVVBQOH369LVr1+zt7TU1NU+dOhUYGAhMg75+/WpgYHDs2LGEhAQTExMpKamoqKjS0lIODg4wyw3a3MrKCkw6QhC0uLgYFRUlKCgIZvs2kpSUJCAgwM3NraCgoKqqevz48bt376alpb17905eXv7OnTtggiY2NlZKSkpBQaGoqAgsdl64cGHv3r1iYmLCwsKCgoKampq1tbVv3ryRkpIKCQkBT8j09LSXl9fBgwdzc3MDAgLExcXDw8Op1jiTk5NIJFJaWjonJ4daTisrq2PHjoWHhwcHB4Mb6unpeejQoSdPnlDLHBERcfjwYQsLC09PTzk5OSsrq5WVFRKJFB4eLi0traamVl5e/t8L43/gTy34+fl5Ozu727dvV1RUbExfWFhITU1VU1NTUVG5cuWKmpqavLy8pqbmwMBATk7OnTt33rx5AxZaysvLtbS09PT04uLiDAwMEhISqAZPnz9/vn37touLS0FBgYaGRkhIyMzMDARBvb29NjY2jx49KiwsDAwMtLCw6O/vB9edm5tLS0uztrZOT0+PjY11dHTMzc0Fo9+mpqanT586OTkNDw9Ty0mhUNBodHJysoWFhb6+vpOTU1lZGTDDyszMtLS0LCwsBL3T7u5uJyenJ0+edHZ2vn792s7OjmqYUVBQ4ODgkJ+fj8FgvL29fX19p6am+vv7nz179vbt219av0xOTmZlZbm4uDx79szPz6+xsXFtbW1hYeH169fu7u5NTU3UI1dWVvLz842MjAwNDR0cHDw8PLKzs2dmZkgkUmFhobOz88Zu5/DwcERERGRk5KdPn5BIpJ6enoGBgaGhoaOjY3h4uKura1hY2NDQEPX4kpISNze33Nzc2NhYFxeXT58+ffv2DYlE+vn5odHoyspKa2vrnJwcqrTIZHJNTY2Njc0vp68/ffr05MmT+/fvG/yDFy9elJeXt7W1+fj4JCQkAOnOzMwA4yJgCrG+vt7T0wOu7uXllZmZOTY2tri4WFhY6OPjA0x6AD09PeHh4bW1tWVlZeHh4Y2NjVSbvKmpqaysrJiYmJGREZCytrbW2NgYFBRUVFRUV1cXFRXV1dVVVFQUHx9PXRGAIGhsbCw3NzczM7Ompub169dFRUWgI4bD4TIzM9++ffuDgdbvxp9a8Gtra5OTkygUamFhgWoQCkHQ+vo6DocbHh4eGBgYGBjo7+/v7u4eGBhYWlrC4/EoFGpubg607+Li4sjIyLdv37BYLMiHmgmZTEahUJOTk3g8fmRkZHp6Gliqra+vYzAYNBqNx+OnpqYmJyc3WssuLCyg0Whg/jk1NUXV28rKChaLnZqa+qXJJJFInJycHBkZwWKxVONcPB6PRqOp9VpbWwNGoMCuFoPBgBcBqAIWi52fn19fXwfXXV1dXV5enpqaWlhY+KV9KwRBy8vLWCwWjUaDeQ0IgigUytzc3PT0NJFI3NiSi4uLExMTY2NjoFJU61dgRkotA2gWsFi1tLQ0NTUFJhFBA05PT2MwGBwOt7GhiEQiFoudm5ubm5sDWYEmAoeBZgSVoua/uLgIEjeWEFinYjCY8fHx0X+ARqMJBAKJRAJmttRMFhYWZmdnNxZ7aWkJGOpS7wsej5+dnd1ocA1slhcXFxcXF+fn55eXlzeaXc/PzwNzZurxq6urOBxufn6eSCTOz8+vrKyAc3+4F8vLy/Pz88AEe2ORgDnDP71xvwN/asHDwMD8usCCh4HZRMCCh4HZRGxGwVO9OIEXKg6HAx6LwIGUQCBQh7LAe5TqxArOJZFIwD+UTCbPz88Dn1bgmUsgEH7pQTk1NbXRXxJ4UFJnE9bW1sA0ONUtB7igzs3NYTCYiYmJ8fFxDAZDdfgDg380Gg1+GhsbA+6oBAJhenoajFQpFMrKygoYu4IR49TUFDgejH5BYVZXV8HAnkQirays4HA4NBo9OTk5MTGBwWAIBAIYZ66trQGnVOCROj09jcPhqB67WCwWg8FQmwhcd2pqijpZsLKyMjs7u7FswKt0o18qGMCDGRNqlTcO5tfW1qhzGWA4De4OFoulVgeUc+OFSCQSmI7ZOHNBoVBmZ2dHRkaGhoZQKNRG/zkIgkgk0uTkJBqN/sGXFtzNtbW19fV14Cn8Kz6QvyebUfALCwvl5eWenp5WVlY2NjZ2dnZWVlYWFhbp6emJiYlubm4dHR3r6+vr6+sZGRkPHz4sKSmhTroQicSqqionJ6fMzMyenp6wsDATExPgMIPBYAIDA3V0dIC7BUjx8vK6cuVKeHg4MCIgk8kZGRm3b9/28/PD4/EQBOFwuOfPn9+/f7+2tpY6M9TZ2Wlra6uurq6mpqampnbt2rXAwMC5ubnV1VU/Pz8lJaWLFy9evHjxwoULp06dCgsLGxgY8Pf319XVpa4e9fX1GRkZOTo6NjU1ZWVlaWhonD179vz58+rq6kgksquri0KhYLFYZ2dnfX39jx8/9vT0IJFIZWXlCxcuXLhw4caNGy4uLp2dnRAEzczMWFtbGxoafvny5cuXL/r6+kgkEnjOVFZW6unpWVpaAtPU9fX1hoaGO3fuXLp0ibrOPDg4+OTJEx0dncLCQpASExOjra0dExNDre/8/Hx6ehNW0kkAACAASURBVPqVK1fOnj178eJFNTW1q1evuru7bzS8DQwM1NDQ8PPzA354ZDL5/fv3Ojo6gYGBIB8sFmttbX3//n2qF3NhYeHZs2eVlJQyMzOpd7C3t9fCwuLQoUNiYmKHDx92cXFBoVDUZ6OgoEBeXl5JSWmjiTQAONuDT8Uf5c3+v7MZBY/H41NSUjQ0NGRkZHh5eTk4OCQlJU+ePBkeHm5tbS0hIZGZmbmysrK2tmZnZ8fJyenm5jY7OwvOJRAI4eHhIiIiNjY25eXlurq6XFxcwHxtbGzMyMgI+L2ARcGWlhZgG3vixAngIk4ikRwdHRkZGfn4+KKjoyEImp6ePnPmDDc395s3b6hTxxUVFXJycjt37jx8+PClS5eEhITExMTCw8PRaLS+vj4CgRASErp48eKVK1dUVVXj4uI6Ojo0NTVpaGjU1NSAIUBdXZ2AgMD169eBVd/u3bvFxcUvXrwoISHBxMR048aNrq6u2dlZbW1tPj6+1NTUDx8+KCgoIBCIAwcOqKqqiomJsbGxmZiYoFAoFAolIyMjLCz86dOn6upqdnb2U6dOtbe3l5aWHjlyREBAIDAwEFjdTU9Pv3jxgoaGBoFA2NnZgbo0NzcrKCj8/PPPWlpawHz48ePHNDQ0xsbG1K8oFot1dHTcvn07GxvbmTNn1NTU+Pn5RUVFU1NTQUegra1NQkICgUAcPny4pKQEtGRgYCAjI+OdO3dAT2RkZOTIkSOSkpIgfAC4EDD10dLSAiVEoVD29vbAXwDca1ZWViQSCV7HwPcBnAJcaKjPDOh2kUgkMpn8T8Oc/FXYjIJfXl7u6enJyspCIpGCgoKMjIz29vapqaltbW1mZmZ79uyJi4sjk8lra2vm5ua0tLSurq5UIz8CgeDv78/IyGhkZFRcXHzt2jUmJqaEhAToH/6SzMzMMTExIMJMaGjo1q1bGRkZubi4gOXs8vKynZ0dcLZVUFDo6ekZHx8/c+YMBwdHfHw8VfDl5eUyMjI8PDyJiYkdHR1Pnz7dtWuXqqpqa2urvr7+jh07zM3NS0tLKyoqqqurp6en+/r6rl+/vmXLlp9++snW1haPx1dXVwsICOjq6tbX1z9+/Bj42338+DE1NVVZWZmWljYwMHBwcPDOnTv8/PwpKSnV1dUKCgrMzMzPnz+vrKxMTEyUlJTk4uLKyMj49u2btLS0qKhoU1NTTU0NJyfnwYMHHR0dz58/z8fH5+npCewXIAhqaWk5fvz43r17d+7cefHixcHBQQKB0NjYCGzgaGlpIyIiyGSyk5PTTz/9dPfuXargx8fHLS0td+3adePGjZycnMzMTGVlZRoaGmdnZ7CiFhERsX37dl5eXlZWVnd3d9CSAQEB9PT0urq6RCKRRCI1NDRIS0sfPXoU2BpMTk6ePn2agYGBl5dXREQE+Di0t7efPn16586dvr6+AwMD79+/t7W1Bb0nCIJyc3Pl5eU5ODh2796trq6+8SO/cUTwmz+gvyWbUfBU+vv7z507t2/fPtAJpFAo1tbWXFxciYmJQPCWlpbAc4Y6wMbj8a9evWJlZbWxsamrq9PU1GRlZQX2qqOjowYGBqysrMAusKur68aNG4KCglZWVgcPHrx+/TqIw2Vvb8/ExERDQyMqKurk5NTa2nr16lVw0Y2CP3DggJCQUHl5OQaD8fX1ZWBgUFZW7ujouH//Pi0trY6OTkBAADDUB/beN2/e3LZtGwMDg4qKSmpqanl5uZiYmJ6eHhA8kC7I/O3btywsLNra2qWlpXfu3BEQEEhPT29ubj516tTevXuphz1//pyVldXR0XFgYODQoUPAoLi+vh5Ep2BgYNi5c6eFhQVVtKurqwkJCTw8PDY2NhcvXjxw4EB0dDQWi21ublZUVGRkZGRlZT127FhTU5OTkxMNDc39+/c32rfY2dnt3r37/PnzXl5eDg4OMjIyHBwc4EYMDQ3p6uqKiIh4eXkdOnToxo0bYH07JCSEg4Pj0KFDnp6eL168AI2vrKz85cuXlZWVjIwMMTExfX19BwcHbm7uoKCg5eXlsbGxJ0+egJLY2trGx8d//PhxYmICRO96/vy5uLi4jY3NjRs3xMTEQkJCfvnMwIL/C9Pf33/x4kVRUVFgAL+8vGxubg561yCQlpWVFSsra1BQ0MzMDDAdIRAIwC/K0dGxvb1dR0eHlZUVdOm/fft2+/ZtVlZW8MHPysoSExMDwWquXr0qKipaW1u7sLAAHnd5efkHDx4cOXIkKCjozJkzvLy8GwVfUVFx6NAhOjo6XV1dW1vbAwcOcHFxubi4TE9PGxkZ/fTTT8zMzLy8vHx8fAcPHnz37h0Khbp58+auXbtu376to6Nz7ty54OBgYWHhO3fuADM1Li4uarCXyspKJiamkydP5ufnm5qaCgoKpqam1tTUKCgo7N27l3pYWFgYPz+/ubl5f3//4cOHjx49Crz02NnZt2zZsm3bNjo6OnNzc+rc29jYmImJCQ8Pz5s3b/z9/UVFRY2NjRcXFzs7Ow8dOqSoqGhqarp//35bW9sbN27Q09NvFPzCwoK3t/eOHTvAB5mXlxd4qlRWVlIolMLCwsOHD587dw74tIuLi3/48GFxcTEyMpKfnx9EB+Lh4WFjY/v555/V1NR6e3unpqaMjIyEhYWjo6NzcnJ4eHiuX78OrOuampoMDAzExcV5eHj27Nlz/vz5oqIiMNd4/fp1MTGx1NRUT09PLi4uIyOjv+5Y/f9iUwu+pqbmyJEjoqKioL+HwWD09PSA6T7QnrW1NQcHh7e3d35+fmRkZH19PYjrAgTf1dV1+/Ztdnb27OxsCIIGBgY0NDSYmZmjoqKIRKKbm9v27dvPnDnj4+Nz5MiRbdu2vXjxYmZmxsXF5aeffjI1Na2urpaTk5OUlGRgYNi3bx/1ohAEVVRUgFOEhIQOHDggLS1taWk5MDCwvLyspaVFR0dnYmICjMkLCwtnZmaGhoZu3LjBx8eXmZkZFxe3d+9eGRkZWlpaY2PjXwo+Pz+fkZHx7NmzJSUlpqam4Av/6dOnkydP7t27NyUlBUybA+8gc3Pzr1+/Hj58WF5evq+vr6amhp6eHvTYZWVlRUVF4+LiwHwY6JUwMjI+efLEwsICRCXo7+/v6uo6cuTI6dOnMzIyHj16JC4uzsDAsGvXLkNDQ6rg5+bmkEgkPT39jRs34uPjs7KyQGgtJycnLBYbHBxMS0srLy/v6empoqKyfft2Ozs7PB4fFRUFxvw5OTnZ2dkgQtapU6eAb+KBAweAT6uZmRmId/b+/fu1tbXu7u6Wlpaurq68vLyrV68yMDDcvHlzfHy8srJSUlIS9H0uXbpEQ0Nz4sSJjx8//v6P5W/KphZ8dXX14cOHqYJfWFgwMjLatWuXm5sbWCjS1tYGLi7Ozs4SEhKenp6rq6svXrzYvXu3vb19d3f3/fv3WVhYQkNDIQjq7e0FnqGpqamdnZ3Xrl1DIBACAgLgW41AIC5dutTf3+/s7Lxly5ZHjx4RiUQkEgl+kpSU/EHwMjIyDAwMPj4+ubm5paWlVDN1DQ0NVlbWtLS0jRUZGhq6cuUKIyPju3fvpqamdHV1wcyThYXFp0+fHj9+zM3NDaIGjYyMGBsb09LS2tratra2GhgYCAgIpKWl1dbWKioq8vPzg3n+8fHxS5cuMTAwBAQEDA8PHzx4UFxcvKWlpaKigp6eXlJSMj8/PzQ0FPSNgdl/QEDA9u3bd+7cKSEhIS0tvWXLFk5OzrCwsNbW1tOnTx87dqytra2hoQEEpfrpp5+MjIyoMWHRaLSVlRUTE5OjoyMIF+Xn50dLS3v58uXCwkITExMEAgHcyPn4+BAIxIULF/r6+sLCwpiYmCwsLEAmX79+PXLkiJKSUlVVVWRkJCsrKx0dnZSUlKioKGjkwMDAhoYGEPkTzP8nJSXx8vIePHhwaGjIzc1tx44dXFxcioqKBw8epKGh2bNnD4iY8HdiUwv+8+fPR48e5eHhqaurAykRERGMjIyioqIPHz4EU+4HDhwoLS2NiopiYGAQFhYGU7tgFnd6ejowMHDnzp1SUlJ2dna6urog3kZLS0t0dDQLC4uwsLCTk5OPj4+Li4usrCwHB0dQUJCxsTECgdDX14cgqLu7G4Q95Ofnj42NpQr+w4cPXFxctLS03d3dGwuMw+HU1NRASAxHR0dnZ2cnJ6fU1NSKigrgtx8eHg5BUEFBAXDy1dfXr66ufvz48bZt286dO2dnZwfeC8eOHaupqRkcHDx//jwbG1tCQgJYF/jpp5/Onz9vZ2d38+ZNWlraM2fO9Pb2jo6OCgoKMjAwlJWVlZSUbN269dChQ/39/TMzM8bGxtu3b9fQ0MjOzlZXV9++fbuZmZm3t7efn5+mpubu3bsVFBTS0tLk5eX37dvX1NQEOj5Afnp6ej8IHviNmpmZ2draysnJ0dPTOzg4eHl5CQkJ8fHxubm5Ad8haWlpVlbWV69eubi4gCgaIJOvX79KSUkpKipGR0erq6uzs7MbGRkFBQX5+fmB4FMqKiqxsbGWlpagajY2NhcuXBATEzMzM6uqqlJQUKCjo7O3t09JSYmPj9fV1d22bZuSkhLVbebvwaYWfF9fn56enpKSEpi0W11d7erqsra23r9/PxMTEwiQ4OfnBzxwrK2thYSEQDwWFRUV4MDX09OjpaW1b98+RkZGZmbmQ4cOvXr1CsTSFBERcXFxoc72hYeHHzx40NLS0traWlpa2sHBAYIgCoXy+vXrQ4cOnTlzJi8vb3V1dWVlZX19vb6+/vz58ydPngTr21QmJiZMTU1FRERAsFpubm4uLi4TE5PCwkJLS0s5OTkwuJiamkIikbKysnZ2do2NjWFhYVJSUvz8/Nzc3CIiImpqasnJySQSaXx83NjY+OzZs8XFxe3t7ffv3xcREdm7dy8PD4+oqOjFixdBYIypqanLly+DpenGxkZ5eXkdHR1QsObmZnV19SNHjpiYmFy6dElTU5MaYaa5ufnatWunT5+Oj4/X09O7fv16c3MzhUIZHh6+e/eutLS0m5sb9QWHw+HCw8MlJCQEBQXBGF5SUtLQ0LC9vT00NFReXv758+fURgCBPZFIZHBw8OnTp6k/gZicJiYm8fHx165do8YshCBocXHR3t7+6tWrRUVFfX19JiYmhw4dkpCQOHjw4KNHj2prawsLC69du2Zubk51N25qatLW1r5161ZHR8dffaJuI3+w4IEBE7BL+/2vTiAQCgoKEhMTwSLtwsICMKsoKSnx8/MLCAhoaGjYOJOck5Pj6emZkpLS3d1NVfLU1FRxcbG/v7+vr29paSmIZ5iZmRkVFbXRXXRwcDAtLS0nJ6eoqAjMioP05eXlioqKd+/ejY2NAcu8lZWV6enpioqK0tLSjUvBEASRyeTGxsaMjIysrKzMzMyMjIzU1NSmpiYsFtve3l5TU0N1usRgMMXFxQ0NDRgMpq+vLzc3NyMjIy0traysDIVCgWVkIpH4+fPn8vJysAvFx48fMzMzgfNmZWUlGo0GN4VIJNbU1FRUVAB7OxB/AhgmkEikzs7OvLy8t2/fZmVlNTY2Uu/j0tJSU1NTUVFRf39/TU1NdXU11Zahu7u7srJyaGiIejCZTO7v73/37h0oQFZWVn19PQ6Ho1Aora2tpaWlG21jJicn6+rqmpubv379WlpaSo20TyKRamtrm5qa+vv7P3z4MDw8vHEtbXJysre3FwSrJJFI379/b29v//r16+Li4srKyujoaEtLy8bA22tra6Ojo319fRu98f4G/MGCX19fX1pa+qPmQsG+KMD5EdjGgnTgL0ndI4EK2HRl4wY4G48nEAhUB1sQB2LjMcCed3FxESwa/+CeSSKRqHasYIloZWVl4y4xVFZXV4H5B5lMXl5eXl5eBur95XuT2l9YW1ujHrzx2QVVpm5Ns7KyAo4BKxQ/HAb24aEWbOMBZDIZvCt/MEdZX18nk8ngEj/U5ZfWqRsLudGsFeTwQyOsr68Dyyjw78YqA/5fn6i/tLXs/xN//Bce3NFN0twwMH8sf5YxPCx4GJjfgT9e8LDUYWB+N/54wcPAwPxuwIKHgdlEwIKHgdlEwIKHgdlEwIKHgdlEwIKHgdlEwIKHgdlEwIKHgdlEwIKHgdlEwIKHgdlE/BvBr6+vw54tMDB/G/6N4ME2Kb/0T4SBgfkr8m8Ev7Ky8gdubQsDA/PrAo/hYWA2EbDg/w4QicT+/v7e3l4QZmd1dRWHw/2wg+LCwsLc3Bx1i7V/Cx6P7+vr6+vrm5yc/KcBZCgUytTU1NevX9FoNDUcJRUSiTQ/Pw9PAP3ZgAX/l2diYiInJ8fb29vV1TUjI2N6ehqDwaSlpRUWFoK93CAIolAobW1tkZGRNTU1/0me4+Pjb968cXNze/nyZXR0dFlZGXU/KcDa2lpXV9fr16/BAb29vT/k0Nrampyc3NPT858IHsTt+s+qC/M/AQv+r83MzIy9vf25c+fevn2bnJx8/vx5Dw+PxsbGu3fv6ujogB11IAhaX18vKyuTk5Oztrb+IQfKP6CmTExMGBsbX7lyJSkpqa6uzsvLy9TU9IfdVCcmJmxsbDQ0NMAWfenp6dQNrQHR0dGKioqBgYE4HG7jtX5ZBRKJVFlZWVBQQI2uB3cKfjtgwf+1ycjIABvXTU1NYbHYa9eunT17NiIiQldXV0NDo6GhoaurKyEhobOzs6Wl5fDhw/v3709ISKirq1taWgI5YLHYjx8/jo2NganZhYWFhIQEEP0ag8GsrKz09fVlZGRQQz4D+vr6zpw5w8nJGR0dXVNTMzAw8PHjx4KCgp6enrKyssHBwVevXnFycqqqqr58+RJE721paXn16lVWVhYOh+vv78/IyCguLn7z5o29vf3JkyctLCwmJyfb29sDAwOjo6OHh4d//8bcDMCC/2tja2srICDg4eEB/rSzszt06JCVlZWdnZ29vX14eLi7u/uFCxf09PTev39/4cKFffv23bt3T1tbmyrg/v7+oKCgzs5OIHg0Gm1tbb1r167Xr19DEITD4TAYTH9/P3X/XAAOh3v58qWgoKCUlJSjo+PXr18jIyP19fXj4uIePHgQFxf34sULWVnZ8+fPq6ioxMfHV1dX+/r6Ghoanj17tr6+vqCg4MyZMyYmJo6OjmfPnhUQEHB0dOzo6DAxMTE3NzczM3N3d4cXg38LYMH/tXn27JmIiIinpyf48+HDhxISEo8ePfL09HR0dFRVVb1y5YqRkZG2tnZmZqaKisrVq1ednZ15eXk/ffoETsFgMDU1NRgMBvwJNoHZsWNHbGwsBEHt7e0eHh5hYWEbY7ZDEEQgEAYGBiIiIpSUlFhZWX19fZ8+fXr+/PnY2Nhz5845ODg8evRITU3NxcXl3LlzSCQyIiLCzc3N1tZ2z549WVlZOTk5YmJiDx8+LC8vd3R01NbWzsvLKy4uFhYWzsjI8PHxOXz4MNgsAObXBRb8X5u0tLSTJ0/ev38fdOk1NTVVVVVfv35tZ2enra0tJyenoqLi7e1dXV3d1NQkJyenqan56tUrHh4e6jaJi4uLKBRqfn4ejJzxeHxQUBAvLy8SiZyens7Ly5OQkLh3715nZ+fMzMzExAQ4q6amJjc39/v3758+fTp//rytra2JicmVK1eioqJOnjxpY2NjbGx85swZX1/fM2fOPHz4MDU11d3dXVlZeevWrW/evImKipKRkXnz5s3CwkJQUND169fj4+MzMzMlJSUTExOdnZ0PHjwI9+p/C2DB/7UhEAheXl7nz5/38fFxcnK6ePFidHR0a2vrzZs3L1y4YGxsfPny5TNnznh4eERFRUlKSqqrq9vb2wsJCYH9MyEIam1ttba2rq2tBYJfX18fHR19+vTpxYsX3dzc7O3t9+3b5+7uXlVVFRgY+Pr1a7DxQ0FBgaGhob29PdiGLSUlJTo6Wk1N7dKlSzw8PGZmZvr6+goKCo6OjocPH753756VlZWKisqpU6fo6emRSKSVldX+/fvfvHmzvLycmZkpLy9vYWFRV1enrq6uo6Ojp6f38OHDX24EAvO/Awv+Lw8Khfrw4UN2dnZaWlpJScnMzMz8/HxhYWFFRUVPT09xcXFERERRUVFzc3N2dnZpaWlDQ0NaWhq1wzwyMpKRkbFxVyyQWFBQkJWVlZWVlZ2dPTQ0hEaj6+rqGhoawFB/YmKisrIyLy+vsLCwvLwci8WOjY3l5ubGxcW9fv3606dPlZWV2dnZbW1tHz58aGhoKC0tffPmTX5+fkJCQm1tbV1dXX5+/tDQ0Orq6tjYWFpaWkFBwdzcXF1dXWJiYk5OztevX/+AptwEwIL/mwA2sfqnP/2wM9S/4If1MBKJ9MOGWb/kh93v/msrbOqlqZtnwfwWwIKH+f/51wvg/3pt/L9eOYeX3H9nYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwiYMHDwGwifmXBUyiUmZmZ5eVl8CeJRBoYGGhvb29paRkdHaVuSzI9Pd3d3T0xMTE/Pz8wMPDly5fh4eHe3t7W1tavX7/OzMzgcLiJiYmxsbHZ2dkfNjOhUCjUjYSXlpamp6cnJibA/idLS0sEAgHetwQG5v/i1xT8+vp6b2/vq1evqBuDjYyMPH78+N69e0+ePAkLC2tra1tdXZ2dnX3//r2Xl1dCQkJzc3NERISjo+PTp08tLCwcHR29vb3Lysry8/O9vLwSExOTk5O7urpWVlZAhkQisaamhrrV8djYWExMTEBAQFtb2+TkZGVlZWtr6/+14xIMDMyvKfjZ2Vl3d/d9+/YVFBSAlK6uLhUVlbt376anpyORSBsbm5GREV9f37CwsJKSksjIyOLi4vr6+uDg4JMnT2poaNTX18fHx+fn57u5uamqqiYnJ9+7d8/JyQmFQkEQRKFQPnz4cPz4cWNjY/CRx+PxmpqaGhoazc3NkZGRHh4eLS0t//X2ZjAwf3t+TcEPDg4aGxsLCQlFRUUtLS1BENTS0iIjI2NkZBQZGWllZeXr69vT06OionLv3r2BgYGRkZHJyUkikRgREXHw4EEbG5ulpaXJycm2tjY7OztdXd3a2lp1dXVTU1MMBgNBEB6P9/X13blzp5KS0uTkJARBExMTSkpKR44cef/+fURERGVlJQ6H+xVrBAPzN+NXE3x/f39ISMi1a9dERUU9PT1nZmYgCCorK+Pj49PT03vw4IGurm5ZWRkWi3369KmioqKlpWV5eTk498WLF8ePH09OTgbD79bW1qdPn+rp6ZmYmDx69Ki0tHRlZWV+fj45Ofn+/ftMTEwnTpzo6OigUChdXV3Hjx/fvXv33bt3m5qafq26wMD8Xfl1BE+hULKyspydnR0cHE6cOGFjYzM8PAxBUHJy8r59+3x9fSMjIx88eBAdHT07Ozs2NhYQEHDs2DFdXd35+XkIgiwsLJSVlTs6OkBueXl5T58+1dfXFxQUdHR0BO+OgYEBOzs7T0/P8+fPKysrV1RUrKysVFZWqqmpsbKyysjIvH37ljrUh4GB+af8CoInk8ktLS3p6emdnZ2jo6P29vZaWlpVVVWzs7PPnz9XVFQsLCzs7u728vJydXX9+PHjxMQECoUKDw+3tbXF4/EEAuHMmTPy8vLj4+MQBK2vr4eGhhobG0dHRyORyAsXLqSmpk5MTGRnZ2dlZU1NTQUGBiooKISFhWEwmODg4CtXrpiamhoaGqqqqhYWFsIzdjAw/4JfQfAYDMbW1jY8PHxtbW1mZsbZ2fnSpUvv3r2rr6+/fv26goKCvb29u7t7XFxcW1vb27dvXVxcnJ2dU1NTh4aGyGRybm6uoKDgqVOnRkZGIAian59//PjxhQsXiouLOzs7VVRUtLS0HBwczM3Nx8bGIAiKjIyUkZGxtrZubGw0NDQ8ceJEZmZmVVXVsWPHbt261dra+r/XCAbm78qvIPjFxcXa2lqwFEckEjs7O2tra1Eo1Pj4eEVFRVlZWX19fX19PViH//79e21tbWVl5ffv3yEIolAo/f397969q6qqWlhYoFAoy8vLzc3NxcXFo6Ojy8vLxcXFRUVFNTU1dXV1YIQ/ODj44cOHz58/o1Coqqqq4uLi6elpIpFYUVFRXFyMRqMpFMr/XikYmL8lf7Cl3Q/ipFAo1JR/urr2nyy5wYKHgfm/+PUt7f7r4yn/4F8c/E9//ddnwcDAUIFt6WFgNhGw4GFgNhGw4GFgNhGw4GFgNhGw4GFgNhGw4H8PKBTK+vr677mUQKFQyGTy6urqD+sgq6urZDL5fw8ZsLa2trKy8iuGHgBNtLy8vLKy8suGWl1dXVpaIpPJv3Mz/hdQKBQikUgkEv+ccRn+PoIHTwzgh4U6CoVCIpEwGMzCwsIfUjYymTw+Pr4xBMhvzfLycktLC7Bu2sj379+bmpoIBML/mD8Gg/ny5QsKhfoV5be4uFhTUwO8MH4AjUZXVFT09vZSY6v85/wnJfwVa0GhUKqrq2tra/+cVt5/H8GPjo66urq+evUqMTExISEBuNxs/NXPz6+mpuYPKRuJRHr79m1ERARw419ZWSGRSL/plwqHw7169aqiouKH9JKSkoCAACwW+y/OXVlZ+bcvpvb29piYmF/m/7+ARqORSOQ/zXN4eDgmJqauro5EIv3nGS4tLf3bV/z6+joGg/l13a5ev36dlJT053Tl+vsIfnBw8NKlS15eXhEREXfv3h0aGoIgCI1GYzCY9fX1lpYWCwuLzMxManissbGxqamp5eXlxcXFxcXFubk58NPc3Nzo6Ojs7CyBQCAQCNPT08PDw+Btxc/v2AAAIABJREFUvb6+PjExMTIyMjs7S+2wLS0tjY+PLy4uggOAmCEIWlhY6O7uBlmNjIzExsZ6e3v39PSMjo7Gx8dnZGTMzc2h0WgymfxDRYaGhr5+/To/P4/H44E34fj4eHV1dVdXFwj7hcFgpqamUCjU2toaHo//8uVLR0fH6Ojoxidsbm4OiUSWlpZCEDQyMlJbWwtcFXJychwdHcfGxrBYLIhZsPG9QyaTGxoaEhMTZ2ZmSCRSb2/vyMgIkUgcGhqanJycnZ2dmpqam5trb2/39PT08fFpbW0dHR3t7u7GYrHfvn3r7u7G4XC9vb2zs7MQBE1OTjY3N7e3t8/NzUEQhEKhysrKmpubJycnUShUX18fCoUiEAjUlwsWi7W0tIyOjh4ZGSEQCEQisaGhoa6ubnp6ur29/enTp2FhYdRgSmg0ur6+vqOjY3JycmxsrLe3t6+vb2pqCtyX1dXV3t7esLCwjx8/rq+vf/nypbu7m0AgjI6O9vf34/H43t5e8G98fHxxcfH8/Hx/f39lZWVvb+/w8HBTUxMajf7+/XtfX9/a2hoajW5qaiovL+/o6Nj43QZXKS8vr6urW1hYWF5ebmxsrKqqsrKySk1NJZPJTU1NVVVVnZ2d7e3tvb29Y2Nj5eXl/f39LS0tjY2NCwsL/f39i4uLWCwWGI93dnaCO/7b8TcRPLDJv3fvXkBAQEpKire399jY2PDwcG5ubl1d3fDwcHZ2tqurq4eHR2tr6+rq6vDwcE1Nzbt370Arp6amhoeHf/nyZWxsrLCwMCcnJzc3t76+vrCwMCIiIj09vby8fHBwsLe3t7i4OD8//927d0A/EASh0ejY2Nj29vaxsbGqqqrx8fG+vr7e3t6Ghoa0tDRwbkZGRlxcXFJSUkJCwsePHx88ePDw4cP6+vqkpCQsFjswMNDZ2UmtS3Nzc2Zm5sePH/v6+jo6OmpqagoLC0NDQ1+8ePH58+eUlJTQ0NCsrKy4uLjBwcHq6urExMTExMTY2NipqSlqa6DRaF9f37q6OgwG8/79+4SEhISEhImJibKyMm9v787Ozuzs7KGhoampqY6ODupLEIvFhoWFGRkZdXR09Pf3+/r6xsbGjoyMJCQkhIWF5efnFxYWFhYWFhQU6OjouLu7j4+P5+Xl+fv7Nzc3g1dJdna2t7d3a2trf39/VlZWXl6ek5NTTU3NyMjIu3fvQDiz2tra7OxsExOT+Pj4b9++AYmur6+Pjo46OTnZ2NgUFRX19vaWlZW9efMGiUQWFxdXVlZqaWm9ePEiKSmpu7sbjUYXFRVlZmb6+fkVFBRUVFSYmpp6enp++fIFvPUWFxeTkpLu3buXkpICegc+Pj7d3d0FBQVubm5v37718fEZHBxMS0vT19cvLCysra199+6dp6dnTExMVVXV48eP37x5k5SUlJSUhEajs7Ky0tLSnJ2dPTw8qKMhMpnc39+flJQUEhLy/PnzvLy8zs7OxMTEsLAwKyurqKiolpaW5OTkly9fxsbGBgYG+vr6RkREPH36FARrCQ4OHh4eTkhIqKioqK6ujo2NDQ8P9/f37+/v/02V8jcR/Pz8/Nu3b42MjO7fv+/s7Jyent7X1xcSEuLr61tTU1NRUeHt7R0YGHjz5k1fX9/h4eGXL19mZ2eHhYWFh4enpaXp6OgYGBjExcXl5OTExcVFR0e7urrGxMS4ubmZmJgkJyc/e/bsyZMnycnJHz58iI2NdXZ2/vz5M7j01NTU48ePIyIiQkNDTUxMqqqqKisrvby8kpOTKysrX7x48ebNm6dPnz548CA0NDQ1NRWE8YuKikpPTzc3N//8+XNoaGhkZCS1LgsLC+/evfPz8yspKcnIyLC3t//w4UNdXd29e/fq6uqeP3+uq6sbEBBgZ2eXn58fFhYGsvX29gaBwCAIWlpaamxsjI2NzcnJyc/PLysr6+jocHd3z8nJKS8vT0pKqqiocHNze//+fV5eXkJCAnVg3NvbGxcXl5CQkJGRkZyc7ODgEBYW1t/f7+Dg8ODBA29vb39//5iYmK6uLiQSaWVllZubGx4e7uPj09nZGRUVdfnyZU9PT3Nz8+rq6oSEBDs7u8bGRnNz85CQECD+vr4+Y2PjDx8+hISESEpKBgcHT0xMgEvj8fisrKz79++bmZmVl5eXlpZ6eHj09fW5urr6+voWFxfb2NgUFhZ6eHi4uLjk5ubm5eWBQVxUVNS7d+8OHz7s6OhIbYHZ2dmQkJC0tDRwl+Pi4nx9fTs7O+Pi4rS0tFxdXU1MTNrb27Ozsz08PHp7e/38/D5+/Jiamvry5cu2trbbt2+D4WFkZGRXV5eTk9P79+9jYmJ8fX2pPbKOjo6kpKSioqKqqipfX18LC4v4+PjGxsbU1NTY2FgkEhkUFNTV1ZWYmJiamurv729iYvLs2TMPD4+PHz/m5eXFxsbW1NSEhITY2tpmZ2f39vampqZ6eXn19PT8pkr5mwh+cHDQ4f9j7z2fGr2y/PG/ZV/tm62tmldT360NVbvrKe+u3WN7PLbb7m537ga6yd3kICSRBBJRAQkJBZQA5SxAOQsUkASSAJEkECIngUi/F6dWpR9te9oz3Z727p5XAj167n3uc8+9557zOZ9TXT02Nra4uDg6OlpWVtbf319ZWdnc3BwIBPx+f0tLy/T0NAaDqaurGx0dvXXr1qtXr4xGo1qtRqPR3d3dXq8Xg8F0dXX5/X4cDkcmk7u7u0kkktFoVCgUVVVVH3/8MZlM9vl8r1696u/vz87Uo6MjHA738OHDr7766u7du1Qq1el0trS0cDgcm81279698fHxioqKv/mbv2loaFhYWJDJZBQKxWAwSKXSgoKChoYGmE+5jyMSib7//nsMBtPc3Dw4OBgIBBQKxdOnT2k0WktLS19fH9D+abXa9vb2+/fv9/f3u1yurN4uLS3R6XSdTtfW1kaj0aLRKJvNHhoa6uvr43K5DodDLpdjMJiXL1+i0Win05k1qlUqVXd3t8ViqaqqKigoGBwcjEajS0tL33///dDQEI1GKy8vn5qaGhoaamxsLCgouHv3bmNj4+TkZCKRaGlpyc/PdzqdVVVVBoNhbGzs1q1bbW1tFAqlpKQEj8fHYjGtVlteXj40NNTd3d3U1BSPx7PGRTQazcvL++1vf0uhUKxWKw6HGxwcnJmZaWhoKCws5PF4fD7fZrMRCIQ//OEPDQ0N4XBYq9XicDgikdjf39/e3j43N5d7XisuLjabzUNDQ//+7/9OIpFcLlcymWxpaSkuLrbb7SUlJSqVanR0tKqqSiwWk0ik6elpMplcXV2t1+vr6+s1Gs3g4CAWi52bm8vPz3/w4MHQ0FAoFMq+IyKRWFVVNTs7i8Phenp6iouLkUikxWK5ffs2gUBobm5GIBA+n+/x48cjIyM9PT3l5eV6vb6srMxisfh8vtbW1p6ent7e3q+//prFYoHdx+FwgH/5/cn/EIU3mUyfffaZ0WhcW1uj0Wh1dXVNTU0VFRXNzc1Op9Pr9TY3N8tkMhaLNTw8TKPR/uEf/uHx48der5fD4bx8+RK82fn5+Z9++ml3d/dXX30lk8laWlpaWlocDgeozVdffXXv3j00Gv3b3/6Wx+PlnuH7+/sbGxu///77P/zhDxKJxG63v3z58sWLF1VVVX/3d3/HYrFIJNI//dM/3b17l8FgvHr1CoFA8Hi8rq6u77///j/+4z/u3LmjUChyH4dEIv3ud7/jcDgIBKKkpKShoaGqqqq4uDgvL4/NZptMpv7+fuDqrays/O6778xmc+5RfHp6+tWrV3q9vra29smTJ+3t7U+fPpVKpa9fvwaLGovFlpeXf/TRR4WFhbk2JIVCef78ucPhqKmp+eSTT8rLy4FltL6+PhgMCgSC//zP/2xoaPjss88KCwtfvXr16aefPnnyZGBggM/nE4lEsVhssVjy8vIcDodYLP7444/ZbPbGxsbr169v377d1dVVWlqKRCKrq6tB/3Mf2WazffHFFwUFBRUVFU+fPr1z586TJ08QCERBQcGTJ0/a2tp6enrq6+tVKlVjY+O//uu/1tXVPXv2rLu7G1Qre8ICmZ+f//jjjwUCwfDw8G9+85tnz56NjY1JpVI8Hi+VSs1m85MnT/B4PIFAqKqqIpPJRUVFvb29jY2NDx8+HBgYUCqVfr8fiUS2tLQsLi5+/fXXn3322Q1vYmdn50cffdTU1PTtt9/SaLTq6ur/+I//KC8v/8d//EcSiVRRUfG73/0OjUZ/9NFHg4ODcKCbn5//6quvxsfHNzc3EQhETU2NxWLJz89/9OhRdXX1d999l6Vjfn/yP0Hh0+n0xMREcXExl8uVy+USicTj8Vit1pGREblcHovFFhcX+Xw+i8UymUwrKysul6u5uZlOpy8tLU1OTjKZTNAWMplcU1NDJBJxOFw0GkWhUA8ePJBIJEKhcH5+nslktrS0gD0/MzNz/d/urrOzM4fDMTMzMzExweVyE4kEuOX6+vooFEpDQ4NWq52ZmYHDgkAgoFAoMpnMarVKJBImk0kgEFgs1uzsbPZxjo+PGQxGU1PT6uqq2WwmkUj9/f18Pl+lUjEYjHA4vLGxodVqjUbj6OhoS0sLCoXi8/lzc3NZa3N5eXlkZCQSiYyPjw8MDDAYDC6XOz8/LxQKhUJhMBgUi8UCgYDJZCqVSiAIBTGbzcPDwysrK3a7nUql0ul0o9Ho9Xohkjc7O4vH40FPZDKZwWDg8/lDQ0MKhUKtVvt8vp2dnWAwKBQKxWIxHJvHxsYUCgWTyRwYGBgYGKDT6QaDYWRkxGaz3XiJS0tLY2Njfr+fx+P19vbS6fSuri4GgyEQCORyuVKp5HK5TCYzHo9DN4hE4sDAgMVi0el0er3+Rshja2uLRqNNT0+Hw+HBwcHBwUG9Xm82m4PB4Pb29szMDIfDMRgM4BT0eDwcDkcul4+PjwuFQrPZvLm5ub6+rlKpeDweHAoGBgbYbHbWGrq6unK73UQikU6nczicYDCo1+sJBAKDwRgeHvb7/QqFoqenZ3R0FA5xgUBgaWlpa2uLx+N5PB5Yc9Vq9fHxscFgoFKpIyMjarX6p6Mn70T+Jyj80dFRJBKx2+3AS58lrk2lUuDzPD8/B18aeFwymUw8Ht/c3Dw/Pz89Pd3f34fpsru7u76+vr+/f3h46HQ6X79+XV1dnT1T7ezs7OzsXFxcHB0dZd/6T3Tp+PgY4v8nJyeADoBwV/bnAFzJvUkmk/F4POCFym6AmUwma6nmwk6Oj4/BLMThcGVlZVqtNhuyAkhC9nP2/vAZevWD3c69ONu309PT3CjdjafOuvpzcSYUCgWBQAwPD9fV1TU2NoJrPZ1Ow30AEfRjQ5c7GrmdAVf/j/X2p+VNDMxb/jYYDCIQCIVCIRQKOzo65HL5n3z1f1L0en1fX99fK0L8P0Hhszi2i4uLHwsg/6yc+XQ6TaVSUSiUzWZ7T9HyH7zt0dHR0NBQZ2enx+P5k3dIp9NjY2MkEgmPxw8PD6+vr7+Hbv6ZMj4+3tfX19/f39/f73A4flbw/IOSZDLJ4/GIRCIej9fr9X85cAvCB3K5/K+FF/z1KfwvMFKXl5fJZHJjY+PNIPk7kfPz83Q6/SYw4/LycnNzc2Nj423wZFdXV/v7+1tbW6lUKjea/bPkPQ3m0dFRKpVKJpNbW1uwmf9KmUvOz8/39vaSyeTm5uaNZevPA/Cdn5+nUqm/FuLz+teo8H9FeVez8/Ly8oYxcn5+fmMSvG9N+Ctq2punjA9fzs/P4X2dn5/v7Oy8pc0ChdWOjo4+nMf89Sl8Op32er0mk+kHt0GTyWQymeDAfHh4aLFY3G73X9Lc2dlZLBbz+XypVOo9vba5uTmNRqNUKrVabSAQ4PF42RIdWbm8vDw4ODg4OPiJlIzz8/ODg4O3gXAfHR0pFAqPx/Nn2AWXl5fr6+tvCQjb2tpis9mBQCD3n1dXV4B6epuT/IcgyWRSKBROT09fX19vbW0RiUTw2l5fX5+fny8uLv5YbsLW1haLxcpFVf2EnJ+fz87OAkjx/cmvT+E3NzcHBwc7Ojp+cJQRCAQSiYSVdWNjo7W1ta+v7y9pLpVKCYVCgUCQxbG9pdzwY4H84BRHo9EvX74UiURUKlWv19+7d6+qqury8vL8/Dx7h729vdnZ2bW1tSwIP/vV5eVlOp0GmO3KysoN51aui+709BR8bKlUqrS0lMlk5l55eHiYvfLy8nJ3dzfX6Mh25vj4eGZm5sZopNNpuHP2TzgNLS8v3759WygUwj0BgHx9fd3W1nb//v3snzeGKLcbx8fHkHmWSqWcTif4sX9wGI+PjwOBAHCZv/lVMpnMNpfJZPb29mBlvLi42N7efjO1IZ1Ob29vw5iEQqHW1lYWi3V4eLiysnL37l2hUHhxcZFOp6GE6eLi4tHR0eHh4cnJSW6238rKyqNHj4hEYnZ9TKfTgGuGPzc3N1dWVpLJZCqVikajIpHozXyndysfhMJfXFzALnp6egpT5/j4OHs63djYSKVSAHq/uLgIBAJMJlOtVuc6peGNLiws4HA4LBYbCARCodDy8jIej8fhcKurq8fHx5lMZnNzc3V1FcpRb21tJRKJtbU1aCUejx8eHmYymaOjo0wms7a2tri4CC+4r69PpVKtrq4eHBycnp4mk0kAmW9sbKytra2trUWj0dXV1bW1tVgstr6+Pj8/H4/H5+bmPB4PoPFhc47FYgDqvlEA7/Xr13fu3Jmamkomk9vb23g8vrW1FXD4ACKAentCoTAej6+trXk8Hr/fHwwGd3Z2ksmk3++fn58HfQgEArk7/O7ubiQSCYVCiUTi+Ph4cXHRbrcnEonNzc2SkpKurq7l5eWDgwMIWzidTofDsba2dnBwEAqFJicnJycno9Ho6elpIpEIBoOBQCASiczOzgKIJXfwA4GAy+VaX19Pp9OLi4sOh8PtdqdSqeXl5YqKisnJyePjY7/fD0G+o6MjOp3+8uVLp9MZi8WyynB5ebm/vz8/Px8IBDY2Nk5OTqLRqMlkAsw84AgUCsX8/HwoFEqn04eHh2dnZ9nQw+zsLBKJZDKZoEXpdPro6Ghvb29zc9PhcKjVap1Ot76+Dr3V6/WAuQZ48szMTHbBurq6Ojw89Pl8Go3GbDZ7vV6FQkGn0wcGBmw2WzgcLikpGRwc9Pv9DocDwPMQJOJyuSaTaXNzM2s3xWKx27dvFxcXm0ym7e1tIHEfHR0VCoWzs7OJREKtVlMoFDabLZVKxWKxWq3+ufvKz5UPQuG3t7c7OzvLysoSiQSw0BsMBgQC0dXVpdFoysrKUChUKBQaGRlZX18XiUQkEmlnZye7jm5ubmq12oGBgbKyMgAtV1ZWqtVqlUqFw+GKiooQCIRKpXI6nWKxuKWlpbW1lcPhoFCokpKSvLy8xsZGHo939+5duVweDodFItHm5mZra+t3330H7/LZs2dNTU39/f1cLndycpJAICCRyPr6eiQS2d7e3tDQ8PTp0/b29u7ubgQCQSKRGhsb8Xg8Fottbm6enJwcHR3VaDSAQqVQKA8fPrwBs5menn7x4kVxcTFka1Cp1IqKCgKBYDAYCgsLHz16NDY2xmKxCgsLI5GIUqksLS1taGjAYrHj4+MdHR2NjY0Oh8Pn8zU2Nt5w/0qlUoDlCQQCoVAIYXkOh7OwsPDkyZNHjx719PSMjIxMT0/T6XSJRNLd3V1dXa1UKjs7OwGO2tDQYLVaGQwGmUzu6upCo9FUKpVCoWSTWCBjZHR0lMlkymQys9lMIBBgnSUQCOPj42QyGdIBOjs7e3t78/PzORxOf3//V1999fr1646Ojuytjo6OZDIZl8sdHR2VSCQGg4HJZHZ1dbW2tra0tHR0dLS1tWGx2La2NoirKxSK7H5+enqq0+kwGExvby+Ao6empuRyOZvN5vF4ZDJZJpO1trZm0a+AY21ra4PmFApFFo+wv78vEAjEYvHw8DBgiurr61tbW/F4/OjoqFwuLywsRCKRGAwGi8VCE7OzsxQK5dNPP8VisdkuXV1d2e32O3fu1NTUUCgUFoul1+tHR0fHx8cBmUOhUIRCYWdnJyC7hoaGBALB+462fBAKf3x83NPTU1RUNDc3V1VVBYPy4MEDNpu9tLRUWVnZ0NAwNTWFQCAikQikK+T+3GAw4PF4o9H44MGDgYEBFotVVlbm9Xo7Ojqqqqra2tra29u5XG5ra6tKpRoaGiovL1er1cXFxQCWfv36NY1G+/LLL3k8nkaj6e7uXl1dffz48dOnT+PxuE6n+9u//dv79+8bDAYWiwVY6MHBwcbGxtLS0qdPn5aXl1dUVAAq84svvmhvbweFHxwcBDg3FottaGig0+k2m00qlRYXF2eP6ECWcH19LZVKnz17hsFgWlpaPv74Y9DtmZmZTz75pLa2dn5+fmJiIj8/f25ujkAgNDQ0yGSypqYmqVTa1tZWUVHhcrmWlpYAXZ87MlNTU0gksre312w2P3/+vLy8XCAQQG0PMpkMKT2vX79ubW01Go0ej6evr6+mpoZGo6FQqKqqqo6ODjQajUQiTSaTWCzGYrHt7e1oNBpqfkETl5eX4XC4rq6OSCTq9frW1tbJyUmhUNjb29vb20sgEIxGY39/P3wYGhqqrKysqKh4/fr1q1ev0Gh0X18f5DVeX19fXFw4nc6ioqK+vr6JiYmOjg6r1Uqn07u7u7FY7KtXrwwGA5vN7uvrA9CeRqPJWgc7OzskEkkkEul0OhqNBguuWCweGxuDnjQ3NxMIhJaWFhKJ5Pf7ORwOgUDQaDQcDgdmV3aHj0ajnZ2dU1NTPB4PjUZrNJpbt27dunVLoVBMTU21tbU1NDSQSCQCgdDa2gqwPLfb3d7eXl5e7vP5svdZW1vjcrk8Hg/QVqWlpVVVVR6PZ2JiAoCSOByuq6sLqqrJ5fKmpia9Xv++s+g/CIUPh8MEAqGpqamtre3TTz+l0WixWIxGow0ODiYSCQ6HU1pa2tzcXFZWBqkmOBwue4pLJBIwTXk83ueffz40NATXx2KxmpoaPB4vEongQ0FBwdjYGB6PLywsXFpaglnudDqrq6tFIlF9fX1JSUlpaSlkWXC5XDKZDFviv/3bv3355ZdsNhuBQDx+/NhkMtXW1g4ODoJNoVAoEAjE2NhYT0/Pw4cPtVptRUXF0NDQ0tISl8stLS0dGBh4+vRpbW3t5ORka2srlUrNbgJHR0dcLndubi6ZTOLx+BcvXnzzzTe/+c1vCgoKACxYXV3tdDovLi7EYnFZWVkoFIIVLRqNQh+sVuvAwAC4kbL5sNfX15eXl9vb24lEoq2trbGxMRaLffLJJ3/4wx9MJpNCoUAikTMzMyqVisPh9PX1ff7550KhcGBgoL6+XqFQjI+PNzY29vT0RKNRiUTyz//8zxwOB4lEdnV1iUSix48fWyyWrNV6fn4+NTX17NkzQO9/9tlnAoGgqampu7tbKpUWFhZOTEzcv3//2bNnUCN0aGioqKiotbUV3otGowFPAbhdpqamvv32W8iB+/LLL0dGRvLz8zEYjFQqvXv3rtVq7evra2hoKCsr++1vf6vT6bJTKB6PFxQUgInR1taGwWB+//vfc7ncaDQKeEc2m72ystLZ2Xnnzh2JRJKXlzc4OBiLxUgkUkFBQTYzIp1OS6XShw8fEonEvLy8O3fuGAyGhw8f/uY3v+nu7uZwOE+fPlUqlWQyua+vD41GP3jwwGq1slgsLBabC5e8vr622WyVlZUmk4lCoXC5XCwW+//+3/8jk8kFBQV1dXUWi4VCoRQXF3d1da2urkql0o8++sjlcr1HNbu+vv5AFN5gMBAIBEC25ufnk0ikUCik1+vb29vdbjeDwYDS0WCZAxY166KPRCLt7e2FhYUoFOqzzz5js9mgZmAb+/1+nU735MkTMplcUlICeOyCggK3211cXNza2gp5S1qtFoFA/PGPf8zPz8fj8QqFAvI9IaUR0trKy8uLioqePn3a19f39ddfczgcOIDF4/EXL14QiUSpVAorVEVFhVgsvr6+5vF4d+7c0ev1eDy+pKQEi8UWFRUpFIrsJrCzs4PBYJhMptVqFYlEY2Njzc3NkB5DJBKFQqHRaNzb29vY2GAwGN3d3TabDc4sOp2OTqczGAyfzwc5c2DmZEvrXVxcLCwsGI3G7u7u4eHhRCKBQCDq6upsNtvExAQOh9NoNEQiEeICpaWl3d3d5eXlGAwmFArJ5fI7d+4gkciFhQWr1fr111+j0ei8vDwWi+VwOPLz8/1+f/bdHR4e0mi0169fj4+P6/X6R48edXV1FRQU0Gg0i8UCEMC6urq8vDwUCpWXlzc+Po7H4ycnJ4PBYEVFRdbdfXp6GgqFuFxuTU0NpNZB+tBXX31FJBKnpqaqq6ttNhuc19Bo9L1797IJi9fX1xsbGzU1NZOTkxMTE2g0mkQiPX36VCwWLywsYLHYBw8e8Pn8jY0NHo/38uXL3t7egoICoVDodDq7u7sHBgaydCnHx8cajQaSmoqLiysqKhwOh1QqraiowGAwJBKpq6srlUrx+XwGg8FmsysrK4PB4MjIiFKpvDGrQ6FQb2+vVCqFVFmv15ufn9/U1JSXl0cgEGw2W2dnZ0lJCZlMXlhY0Gg0z549y55u3p98EAq/urrqcrlCoVAsFjObzePj45Ag6fV6IRt5YGDAYDCoVCqHw2GxWHKX0tPTU5lMRiAQ/H4/aM7MzIxUKl1bW4tEIvv7+6FQSCAQhEIhAoGgUCjAIKdSqQ8ePHj+/Llerz8+Pg6FQhQKZWRkxG63m0wmnU4nlUpnZmY8Ho/FYkkmk2KxGNJsBwYGJicnxWIxAKSBR2F4eFgmk83NzcViMeBp8nq9sVhMKBQODw+Db0+n0xmNxqmpqdXV1exqdXJyEgqFJBIJi8VyOp1HR0fBYDASicRiMbfb7ff7IXdqd3fxBROqAAAgAElEQVR3bm4Oci3BAnc6nel0enl5GdxgqVRqaWlpbm4u1x24tbWlUqmUSmUqlcpkMuFwWK/XLy4uQviHyWTabDbwk7ndbp/PB+X6AoFAVVXV/fv3//mf/7murm5mZsZqtQKcfm1tbWNjY3x8PDcQcHh4ODY2Njw8vLy8vLW1BQ4wIMaIxWJKpTKRSIRCIbPZbLfbbTbb1tZWOBxeW1vb3t52OBxZm/z8/Hx5eVmr1Wo0mo2NjY2NDY1G4/f7rVZrLBbb2tpyu917e3ter9fj8YD3EcI04LM4OTlxOp3JZDKRSPj9/rW1NYfDsbq6qlQqKyoqXr169cc//nF4eBgoBlZWVmKx2N7e3sLCgslkikajuQirg4MDh8MRi8U2Nzdjsdju7i5wnKyvr+/u7gIie319fXt7++DgYHV1Ffz5b2a5gfMvFAptbm5CrCSRSCSTyaWlpXg8rlKpysvLGxsbP/nkEwwGk0qlVlZW3hPQK1c+CIW/uLjI4qszmczx8fH+/v7BwQGEgoB5JpPJADdgOp2+EZU5Ojra3d0FlDsg2E5OTrJhpLOzs+Pj4/Pz893d3aOjo7OzM6/XCznz8/PzsNmenZ3Be4WYEHh3oUugnCcnJ2dnZ6enpxDOSafTp6encMHl5eXh4SF4+AE6dnZ2JhQKq6urh4eHs85FCEAA3ibrVwNQ8MHBATDMXP83Wh5ukn39EKLb2tqqqqrq7u5eXl6Gkx5MKeghPG+uxw7unOt8Pj09haGDWBT8EMKH5+fn8Cw6na68vJzL5TY1NTU3Ny8sLFz8t2R5Jm+0Ai8LLoAEAfgMgwlPlMlkskkBMAjwULnvEUIkMA4wAtlbwd2uc6KDN0KecAH0MHtBIpGgUCidnZ0ymaympobL5e7u7uZCD4Ce6E0wwjsECPwg0dX+/v7Y2FhlZSUOh3v58uXw8PC7au5Pygeh8L+wzM7OYrHY93pestvtAoHg3cZUt7e3Icf+Hd7zTQHeHrPZ7HA4wuFwbnT9VyfHx8fBYNBut4Oxtrq6+oEwyWYyGTCm5ufngZnrF2v616Tw7wSSCaSFMzMz6+vrN1ic35VcXV1BMP/d3haMnWyy3Vv25M9oKJPJLC8v/+XMtu9kbP/ymwCm45dU9Q85R+BXpvDn5+eJRGJjY+NdDeh7Uvh3e/Pd3d1oNDo/Pw8TFxzaqVTqT1qeV1dXiUQiEon8kiDW09PTxcXFeDz+rhT+6uoKqER/btbd+9a6VCoFOKI32wVawdwo3Z8UmN7vm8j816Tw19fXp6enLBaLz+e/5fXZQ/ivV8D1NTw8zGaz5XJ5MplMp9M2m00mk70N7losFqNQqF/SMt/b2+vq6nqH59KrqyuTydTe3v5Lmr5vI0ajsbS0NBvSuyFKpbKwsPDtgTRXV1eAxnt3HfwB+YAU/uq/5c3/59I5YLFYDAZzw7y/sS5m/wyHw9lQx1WO/EQHfqx7b9Y8yf5546s3G8r9/BP3+cHW6XQ6Go0G8haRSBSNRjOZjMFgoNPpPz2ZoNHR0dGmpqYsTcWb/fyxPoNf7c0b/lhb2ec6OTlpb2+n0WjZ/9/gz7jRxI8NVK7Y7fba2trFxcXcK3/wtyBv7pNvlie50f8bH67//xPy6g25vr62Wq1VVVWxWOzNPlxfX+t0uqKiotxvc58XkrtgS4cLjo+PI5HImzwf71Y+FIXX6/U9PT06nY7L5Vqt1tnZWbfbDS5fu91Oo9GUSiW4shkMRmlpKYvFAi6aVCql0WgYDIZMJtvd3Y3H42NjY3K5HCJhDAZjZmbm6OjIaDRyuVyv12s2m2Uy2cnJycrKSiKR2NnZ2d7evrq68ng8YrEY4m25x+90Oh0IBKRSKY1GUygUgL0XiURAeDQ3N2e1WgGJCSVT1tfXpVIplUrl8/lutzsejyuVShKJZLFY9vb25ubmJBLJ4OCg0+nc2NiAEiVMJlMulwNTXZZ3NXdkCgsLu7q6oHgOBBpZLJbVav2x3eDy8nJtbU0ul5NIJBQKxWAwUqmUXq+nUqnAIS8SiWDJYLPZQDivUqnYbDaFQlGpVJlMJhKJjI6OArdvtp88Ho9AIMzOzuYeEK6urhYXF+VyeUdHx8jIyNHRUSAQYDAYHo8H+JvYbHZ7e7vZbN7f31coFBwOx+FwnJ2dJRIJYPhiMpnBYHBxcZHH47HZbAKBYDKZch/n4ODAaDQ2NTUhEAi5XJ5Op7e2tgBFNzAwMD09vby8TKVSgVXKYDBEIpH+/n6gnfL7/aenp1arlcPh4PF4jUZzI34WiUQGBwcBXcvhcBgMBgys3W4nkUhSqTQajc7MzNBoNCQSSSaTAUJjt9uvrq6kUunvfve7kpISoK9JpVJ0Op1AILjd7t3dXaFQeOvWrfz8fAAIxeNxNpsN3QAPIoPBGB0dBaK+zc1NJpPJYrHW1tb+AjX60/KhKHxPT88//uM/MpnMsrKyuro6LBZLIpFgIgoEgv7+fmBB93q9jY2NL168aG9vHxoampmZ0ev1AoFgaGioqqpqfn6ez+e/fPlSq9UuLy+TSKS+vr5EIjE/P19WVtbT0xOJRAQCAbjoKysrORxOPB632+0Oh0MoFAIMc2BgINcA3t/fl0gkNTU1HR0d/f39IpFoeXn50aNH9+/fl0gkIpGou7tbJBIhEAgOh7O+vk6j0QQCQWNjY2VlJXDd5eXlPXv2zGazBQIBEokEqFgmk7mystLT01NbW5ufn19XV1dTU/PgwYM3ackzmQyZTL59+7ZYLIbjiUKhaG9v/wl7PplM8vl8gAAikUggxu/s7AR0ajQaLSkpqaqqAhZqnU4HjHHAmt7b2zs7O8vhcIBnvry8HFi9q6qqKisra2pqdDpd7lka2pLJZHV1dVVVVevr6xwOZ3x8/ODgwOPxAOPd48ePKRRKJBKBlQt4hEUiEYPBaGtra2trc7lcEonk008/xWAwBQUFZDI593FmZ2cBF1RcXEyhUPR6vUql4vP5Uqm0qqpKo9G4XC4ANd+9e5dGowEvlc1m6+vrGxsbC4fDAwMDAoEA6IZv8A5otdqPP/64vb09Pz///v37ra2tgGLq7+///vvvsVhsOBxWKpUPHz68detWUVHRs2fPfv/738tksuXlZTqd/urVq+LiYhqN5vP5RCLR/fv3Hzx4YDab3W43iURqb2+/ffs2iURyOBwymQy4dwsLC1UqVSgUev36NZFIvH37Np1Ohz95PN6NxKp3Lh+Ewu/t7fX09Dx58sRgMLx8+bK4uLitrQ2NRuv1+u7ubpfLpdFoUChUIpHo7e3Ny8uDIyKNRgNli0QiKpWqra1tZWWFy+W+fv3a7/dD2hmPxzs/P4/FYnV1dWQyeWNjIxgMEonEhoaGv//7vy8uLo5GoxqNpra21mg0ulwuQL/nTuj19XUGg0Gn04FrHUij7927h0QizWYz5KLs7e0hkci2trbFxcWWlha5XD4wMDA8PJxMJicnJ0tKSvh8/urqqkwmo1KpoVCor6+Px+MtLy8jkcjOzk5IFujs7Kyurs6N5J2fn6+urh4dHSWTSQwG891338HxRCqVtra2/tix/OTkRK/XQ1UGHA5HpVLNZjPwZ6tUqqWlpZmZmSdPnmAwGAKBIJVKp6amRkdHWSwWl8uVyWTAP8lkMufm5gYGBpBI5MrKSnV1dV1dXV9fX19fXzAYzAIEksnk6Ojo8PDw3NwcjUbDYDBra2tdXV02m212dnZoaMhisczMzDQ1NfF4vKWlJRwOB6UdILVhcXGRSqWCcTQwMHD37l2ZTNbV1cXj8XKfSC6XFxUV4XA4wNj39PQAmaxWq+3v73e73ZOTk8+fPx8dHW1oaODz+Ts7O0KhkMfjAfkki8WCwiEoFIpKpd4YK6FQ+M033wwPD1dUVOTl5XE4HDabXVdX19LSgsPhxsfHU6kUhUJBoVDwz56eHgAXKxQKPB6/uLjI4XDApnv16hUKhert7YUULwKBEI/HsVisSCTq6upCoVDRaHRkZKS9vd1isRiNRviARqPlcrndbn/x4kUuhPE9yQeh8KA5Op3O5XK9ePGir69Pq9Wi0ejOzk6gmsXhcAgEYmFhobi4eGhoSKvVolAonU5XWlrKZrOBSHxsbGxubs5ut8NyEI/HoRDK2dnZ0tISkMMbjcbt7e2BgYHHjx9//vnn5eXlwWDQ7XZ/8803Wq2WQqFUV1eHQqHcg9zc3BzUTtFoNHQ6fXJycmRkBIq3BAIBPB6v0+n8fn97ezuPxzs4OKDRaFAFZWFhYXV1taenRyQSHRwc+P1+IpEok8lGRkaqq6tlMpnP53v9+vXU1FRHRwcOh3O5XEgkMptJcn19fXh4SKfTtVrt1taWRqN5+vTp7Ozszs4OlCgBe35rays3cfD6+npjY4PFYiEQCC6X+/jxYzKZ7HA4Pv/8cx6Pt7q6enZ2Zrfby8vLQ6FQT08PgUDIZDIWi+XOnTuFhYWhUMjn89XU1PD5fJFIVFtbC8Vhqqurx8fHx8bGampqcndIv99fVVUFCWdVVVVUKnVpaam5udlqtYIh43a7oRaAUqmEbN+2tja73Q6QQZ1OV1BQoFarPR5PT08P8MaSyeRck/7q6orBYDQ3N8/OztbX1xuNRiqVWlRUZLVaS0tLwX4eHR3l8XjBYBBg0ZlMZnR0ND8/n8lkUiiUmpoahUKh0WgKCwvpdHruxIPiM2QymcViQdU9AoEwPT1dXV1dW1srEokSiUQ8Hq+rq1OpVDQaDQDz5eXlNptNLBZD7bDe3l7Y3l++fMnhcIxG4/HxMSz6fr8fi8UGg0HIIJDL5U+ePOnv77fZbHw+H1h60Wi0SqXS6XT37t2LRCLvQ79y5YNQeLVaLZVKE4mETqcTCoUqlUokEkH5pKamJiwW29TUBNTRWCzWZrPp9fry8nKj0YhCoQoLCyElDg6lZDKZTqdPTEwAHTos7SMjI1qtlkQizczMbG5ujo+Pq9VqLBYrEAjS6XQ0Gi0oKEAikWg0emhoKJVK5fbN4/Hcvn27p6cHSjgsLCyQSCS9Xg8kCkqlEofDtba2wuFwaWmptrb266+/RiKRsVgsGo22tLQAEHh1dZVIJEIZBiqVajKZYIICEHhkZMRoNA4ODua6fE9OTng8Xk9PD5lMZjAYWq328PCQx+M9ePBgcHAQ/FJ0Ov3Gfnh6eqpSqWpqahgMRmNjI5/PD4fDDQ0NjY2NFosFLG2pVLq7uwvZbPF4vLe399NPP/3uu+80Gg2UwUMikYODg3w+f2JiIhwOi8XieDw+MTHR1dWVG/VIJBIkEqmsrAwKTmg0mkAg0N3dPTU1NT09jUQisVgslUoViURA/Ap1AdbX1yUSyfPnz3t7e1EolMfj0Wg0ZDI5lUrZbLaxsbFc6PTFxYVarZbJZMlkEofDGY1GlUoFeRB4PN5ms1ksFqVSCaMtlUr9fn86ndZoNAgEYmpqan5+vr29vba2ViwWk8nk3Hyb6+trr9erVqv9fj+wems0GhKJFIlEDAZDfX19d3c3ODi4XO7CwgKcO+bn56lU6tzc3MLCAo1GY7PZZrP5+Ph4eXmZQqH09vZ6PJ6Liws4FkH9qUwmA8h5Op3O5XLdbrfL5bJaraurq3Nzc/C8YHj+AmGID0LhgeLi/PwcnFLb29vgUYNDu9/vhxJ/h4eHQNiwubkJnFPRaNRms4Eebm9vz83NQcm+3d3d09PTmZmZeDy+v78fjUZhqT4+Pk6n0/Dt2toaeESBEWF6ejoUCm1sbOR6pE5OTsBdBNXRjo6OTk9P5+fnYZe7urra2dnx+/1TU1P7+/urq6ssFmtwcNBoNGIwGDabDSUKYSvOZDKLi4tWq3VpaWl9fX1nZ+fw8BC6urW1BejxtbW1XHUCMqnZ2VmfzxeNRuGgMTc3Zzabs749r9cbCARuOJ+3t7cDgcDKygoUgQTqC4/Hk0gkzs7OAKp8fn4+Pz8/Pz9vMBgaGhrkcjmVSiUQCIFAIB6Pe73excXF7e3tnZ2dg4OD3d1dYF9cWlq6QcUXj8cdDkcwGAR4+e7u7sLCwt7e3vHx8dzcnNfrjcfjUDZzYWEBSPWvrq6SyeTU1FQoFAKWkUQiAZUkgCk897QCaX87OzvANZZKpba2tqA8IzxaKpUCfPvh4eHm5mYwGORwOIODg9PT08AUDrqaSCQADJ87ULu7u6lUKp1Ox+Pxk5OT3d1dyIYAlptgMAhoa+BfAQDPwcEBtHtxcQHcJ9BbeFlQqfL6+vr09DQejy8vLwPg5/DwcGlpKRaL7e/vn56e7u7uHhwcXF1dHR4egiv6+Pj4xtx7T/JBKPwHK1CBlMPhvA2F2+rqqkAg4HA4er0eyrD8Aj0E+bFo09vI1NQUDodTKpVKpVKtVv9YVPnXIl6vFwqEvW8Ey69U/k/hf0rC4TCPx7Pb7W8Jh8jGtywWy/sOqObKX6LwZ2dnUHDGZDK971rFv4CsrKxEo9G/di8+XPk1KfzV1dXp6WkuSeD7awgyujKZzFtmLGY5JwH6+rPg7pBI98vvSNA05PnlEmb+MnJ5eQkJiDeS/H5Mrq6uwPT96SSF9z03rq+vDw4OIH3z5/7w6urq7OwMUjbfR8feRn5NCg8e5rckCfhLXjxwpEImUyKReJtbHR4ehsNhwN78XHG73Xa7/a8CAZ6amhobG3vf1Mg/KJAAbzab3xJ8enp66vP5DAbDD/LS/mKyvb2tVqsnJib+jDpwmUxmZmZGrVb/efPkncivSeEPDg4wGMwNBsgfu9Llcv3ZRvXl5WUkEuno6Ojo6JDJZG9TyCmVSgkEAoFA8Gcs/HQ6/QZj9DuR09NTyLRPJBJZRpcbIhAIEAjEj337vgVc6MD3fnFxcXBw8BNmzunpqd1uHxkZAR/+1dVVKpVaXFz8JY9OiURCIBDYbLZYLPYTmTzr6+s3Yj0g6XRarVbz+fz3zUX9E/JBKHwmk1lYWPD5fOvr66FQKJlMgjMZvvJ6vS6X6+Tk5Pj4uLa2lkQiJZNJOFRvbGxMTU2Bxx4c78BMMjU1pVarwfvt9/s9Hs/09DRkNQGMGQ6r4O+NRCLb29u5Bi2A1WtqashkMp/Pf/r0aTgcPjk5CQaDKysr4KhfW1tLJpOrq6v7+/s+n49Go/X09BiNxq2tLZfLNTMzA8bq6upqMBiEepUrKytutzsYDO7t7e3s7ACb9dHREZFI7OjoiEaja2trmUwmEAiMj4/Pz88nk8np6WkwNLxeL/RwZ2dndnbWaDRqtVpwsG1sbLjd7qWlpZ2dHWD7jsVi4XAYj8crlUqTyaRUKuPxuM/nC4fDQIy7vLw8OzubTqcFAsFXX30FRZ2vr69PT0+9Xu/ExITb7c76+U0mE2yqa2trk5OTTqcT0u+A4dPv9wMn98rKyurqqtPphLFdWVmZm5sDYvlMJrO7u7u9vX15eRkIBCwWC1wPJdn5fD7AYLFYrM/nm5mZAcw8sJJnX8rx8TGfz6+srKRSqTD4XC7XbDan0+nNzc2JiQkg/7HZbKFQCHDpx8fH6+vrOp1uamoqEonkprVdXV35fD6XyxWJRFwul8/nm5qa2tvby2QyEDMDgnB4KIPBMDc3Nz8/j8Vinzx5AtPMYDA4nc5wOLy/vx8MBrVaLfCFj42NCYXCGwhZiOao1WoEAmGxWKBXUIobCI6cTqdCocjS+Lw/+SAU/uLigs1mP3/+nM/no9FoIpEIkdudnR2v1ysUCgEpvby83NDQgEAgRCKRVquNxWITExMcDgdwoCaTSa/XGwwGs9kMxKwLCwtACUyhUMhk8tzcnE6ns9vtx8fHLpcLUDrAK2oymXLxJKCEjY2Ng4ODeDy+p6dndnY2EAh0dXWxWKytrS0ulwukxSMjIwqFQqvVFhUVtbW1LS8vGwwGiURCIpFMJtPy8jKLxRobGwNiI7lcLpfLgY3L5XKh0eixsbFIJEImkysqKiQSSSAQsNlsIpEIh8MB+THQYwMHK2wpUP+4sbGxq6tLKBRaLBaVSkWhUEZHRxcXF4EdVaFQ6HS6L774AnBsRCJxY2MDj8cDZBCNRnO5XBwO5/f7ZTLZ7du3kUikUqlcXV0NBAJcLre/v7+5ubmzs3NoaIhEIgEZ8/j4uEwmI5FICARCrVZPT0+r1WoymUwkEp1OJ4VCGRgY4HK5zc3NMNehLHQikeByuZFIJJFIwDoiEokoFIpUKlWr1QwGQywWMxgMjUYzODj4zTffqNXqwcFBADXodLrcKNrOzk5VVVVxcXFdXR2Px4tEIjU1NVardWdnB8L4tbW1fD6/u7ubTCbv7OxwOBylUgnlwHk83vDwcO6+enFx0dzc3NDQQCaT8/LyBgYGMBjMyMgI8JdSKBQsFtvd3T00NDQwMNDZ2SkSiSQSSXl5eV5eHmQW0Gg0KBctFosVCkVbWxuJRNLpdPfv36dSqbnT6eTkxGKxABHYw4cPZTKZ1+tlMBgUCqW5uRkGGYVCtbe3t7W1vW9auw9C4TOZTE9Pz0cffUQkEr/99tvvv/++rKzs1atXGo1GIpFAwgkAVOvq6gC9WF9fPzAwoFarLRaLQCDA4/FUKhV4pg0Gg0wmEwgE09PTAL9VqVRcLpfNZn/99dc1NTVra2symay/v39iYgJCaDKZLHdlPTo6qqioKC0tBYj7xMQEj8djMpkdHR00Gm1zcxOHw7148aKjo6OzsxNICLu7u4E0FlZ3wLS43e66ujrYruVyOZQowWAwRqNRLpc/fvyYyWROTEzU1tYWFRUB4RyRSHS5XHK5HIfDAbIQhUJhsVg0Gg0K73Q68Xg8m802GAzd3d2PHj3C4XBarRYgxnV1dQ8fPjQajW63G4VCORyOyclJEom0trbW0NAwODiIw+Hu3LlDIpHq6+tpNJpEImGz2Vqtlslkdnd38/l8p9M5Pj7e0tJSUlICGQTDw8NCobCgoADSWhobG61WK4VCkUgkHo8Hg8H4fL7W1tZXr14NDAw0NTWBwjudTiaTyeVyv/jiCxaLlUgkWCwWrDJqtVqr1Wq12uLi4ubmZrPZvLCwoFAoGAxGKBRiMpl8Pl+n0+Hx+Ow5+fLycnl5ubKyUq/Xs9ns5ubmWCwGlNjj4+PDw8OhUKi6utpoNIrFYgwGs7S0xGAwysrKJBJJLBYbGRmh0+m5h//z8/OioiJg7/z4448HBgZwOFxeXh6VSg0Gg6Ojo2QyubOzs6KiAoFAwGuSSCRjY2N8Pr+pqclms9lstp6enp6enoaGBuBNxOFwPp8PAJ3Zhi4uLkwmEwys2WxGoVCvX7+WSCTA44jH41taWiorK7FYrEKhIJFI/ysU3ufzdXZ2DgwMOByOu3fvwkH92bNnr1698nq9wWAQmIZra2uZTObo6CiQvRcXF3u9XoFA0NHRMTMz4/V6S0pKpFIpoJoWFhYODg7a2tpQKNTi4iLwK0NuE6RboNFok8mkUqnKysoCgUAu+8329nZxcTGLxZqfnx8eHm5vb//973+fl5cnEAigTlB5eTmTyRSLxUgkEoqiIJHIR48eNTU1hcNhn8/X29sLNl5tbS3shJAtI5PJYH0RCoVisXhpaYlEIn3++ecIBMJut8vlcg6HY7fbiURidXW1yWRqa2uD9CEMBgNePagDAQTSFArl888/f/78uc/nW1lZUalUvb29Op0uHo9LJBI6nT4zMyORSBgMRiwWKy4uHhsbEwgEL168AK5eJBKp0Wjm5uZGRkbGx8chSWF2dra9vX1wcPDFixednZ06na6np8fpdFKpVCCfHxoampiYGBoaAlbPkpISu92OwWDIZLLT6USj0QChiUajXV1djx8/fvjwIRqNdjgcExMT7e3ti4uLJBKJz+d7vd67d+++ePEC8LwMBsPr9c7MzADL+KtXr+RyeXafPD4+djgcVCp1dnZWoVAQicRgMNjZ2Tk4OAhQdpvN9uTJE0iIQCAQAoFAJBKVl5eLRCK9Xn/nzh2ZTJbLxre3t1ddXY1EIoVCYVlZWW9vL5/PLysr6+joCAaDxcXFYMTV1dVZrdbW1labzQZk+2azuaioSKfTMZnMP/7xj1DawO/3Q3kSj8fT3NwM7GnQViaTQSKRNBrNbrfX1dUNDg4+evSIwWC4XK7a2tqxsbG6ujoSiTQ5OdnV1aVSqd4kw3y38kEoPJ1O7+npCQaDoF2jo6NqtbqmpubWrVudnZ2Q8gU84VNTU3ANhUL593//dxQK9ejRo/Lycr/fPzQ0dO/ePYvFIpPJHj9+HA6HJRJJcXExiUSKRqPAtV5UVNTZ2Qnpt1DC7dWrV19//XUkEpmfn4dz7P7+vkgkunPnDh6PHxsbw2KxQqHwzp07//Iv/wIQerfb3djYOD09bbFY7t+/j0KhXrx4UVRUdO/evS+//BKDwTQ3N9NoNBaLVV9fj0ajDQYDEoksLS2lUCj19fU8Hq+7u5vJZAJuD41G19fXt7e3FxcXV1ZWPnnyBIVCoVCogoKCrq4urVYL5h+NRgOHVm1tbWFh4eTkJJ/PD4VCZWVlv/vd74RC4dzcHBaLVSqV5+fna2trOByOQqHAWgOqCEYQ8M/39fX19PS0trby+XzA2EEdi6+//rq1tRWgu3V1dSKRaGZmpqqqCvrw3XffQe16u91eVVXV2tpKIpG++eYbON243W6DwdDc3AwowJWVFaFQSCQSe3t7RSJRPB7X6/UvXryg0WiNjY1DQ0MAwq2qqhoZGaFSqVgs1mKxDA8PIxCIJ0+eQJaETCYDP8X+/j5QBhMIBLlcDj4aHA43MjLS29vb1NREp9OfP3/ucrm8Xi/Air1eLxS9QCKRX3zxhcViMZlMUFkUwj1QTkcikUil0ubmZi6X29DQAPvN3bt32Ww2jUZjMBirq6tlZWVWq3VkZASFQs3MzDx+/LiyshLKkBCJxOLiYgKB0N7ejsFgJiYmkEikwWCYmpqyWCzX19eXl5dtbW1w4mtsbBQKha9fv66oqGhtba2srJV8U8AAACAASURBVAQe8cnJyXA43Nraarfb3zkz2g35IBTe4XAAOlWv1weDwWAwCPYPh8MZGxuj0Wgqlcrr9YrF4p2dHajf4vP5KBQKh8OBXJqFhQWRSAS1qLxeL5vNBjLGsbExj8cDqNVQKGS3230+HwAqaTQanU4fHh6GtLaVlRWITu3u7orFYqg6MDIyAudJk8k0ODgIXNTz8/Mul2tra2t1dZXH4wGaXaVSQdUhNpstFouDwaDFYmEymXa7PR6PW63WsbExqVSqUqkAqu3xeK6vrzOZjMlkmp2dtdvtFAoF8N5CodBsNisUiomJCfA7OhwOSJvd3d2F6jQejyccDl9eXkIiisvlWl5e1uv1oB7b29swuWEk3W53LBZbWFhwOBxAnKjT6eACj8fjdDqhqp/VaqVSqSMjI1Ap1WazQZ1DuVwOygZeAIDfikQikUhks9lGR0cnJiZWVlb29vZCoZDVagXQ6N7e3vr6ejKZnJ2dhSjAwsKCQCDQarV6vd7n821sbMRiMbCNjUajzWaLRqOQhabRaKxWq9lsZjKZkE8CtFl2u12pVEYiEXCgwlOD18Plco2Pj4Np3dHREQgEDg4OINNJoVAAWzaQlMOwz83NLS4uBoNB4JA0Go0+n89kMrFYLPAfzczMgPtwb29PrVbbbLaRkRGBQLC9vQ31sKRSqdVq9fv9XC5Xq9XCHI5Go0ajMRgMmkwmg8EAmzxg9aVSqdfrBap/iUQil8vdbvf6+rrf7wfML/z5v5HiClirc/8EjPGbrCy5AtCRG3wyN271NpLJZFKp1Pr6eiKReK98Qz8XKXB2dqbX6wcHB3+6APb7QJ4YDAbwpUEZLzDa33cfLi8vo9Ho24cM0+k0jI/Vav3BC9bX1/+MAOTFxQUQ5uv1+reEDKTT6WQyubu7+wuggH6ufIgK/3/yg3JycgJ5db98FDcej4MfSyqVOhyO9827lpWfWN/flEQiIZVK7Xb7j22Sb3+rXDk5OTGbzVqt9mcBfj5AVQf5P4X/1QiUfIBEt79K01tbW0DD9gu3/pYC2I13DljMFhr5QDjt/0L5UBQ+nU7v7OwcHx+/7zPMX2XpPTk5gTLsP9g6FK5PJpN/lQQvoLvPYplu9ArKJP1inQG8DawsP90uZMu+b0Ko6+trSPh9k4saBLwJfy2o4p8hH4rCB4NBNpt9g23mXcnOzg54ZbKFpaAk2DtsAqbpj90TYCpLS0s/+HSXl5cqlYpKpf5VcioODg7cbvf4+HgikbjRK6DH/oUVPhAIaLXaPxmOTqVS/f392VqUP7eVzc3NG2Wn3hRgXojFYr29vcCY+qYkk8murq5fgJrqXcmHovBKpbKgoMDpdB4fH8O8h9QiQML+STMSSpfd+Ofe3h4szNFotL6+XiQSbW1tnZycJJNJt9v90xhsyCG7zilmdv1D1gHAWre2tpaWlmZnZ6HyXO5PILzP4/EQCETWmQTpcdmbnJ+fU6nUsrIy8AkdHR0dHR1BPw8PD6Fa3vX19cXFBdQhvLEuHB0dAT8EXAkpaPDV5ubm+vo6XH9ycrK5uZnFF8Gtrq6u4vE4l8tVKpVQTi8ej8MGm8lkWCxWbW3t8vLymwvZ2dlZMpnc2NiA3mYyGaCIAHshG1Y4OzsDopGLiwu4Jvs2T05OgGPjBok1lNDV6XTZlw71c6Ho4OHh4f7+Ptz2Bqbt+Ph4ZWUF4MnX19fb29uxWAxIAWHM5+fno9EosHGYTCYom5dtd3t7Ox6PA5b2/Pw8mUwCM9/8/Hx9fb1AIMiigCC+sL6+nk6nV1dXKysrJRLJ3t5etsNA5ZJMJs/PzwFVDQVUIOoBLC+Ag4bOHxwcRKPRWCwWj8ff7T70pnwQCn95eSmVSl++fKnX651O58rKyuHhod/vN5vN29vbwWAQiGKAzHhxcRGqcAYCgaOjo8PDw1QqFY/HDQYDILFXVlZOTk4ikQjATldWVhYWFpqamgC7ajKZzGZzKBRaXl6ORCKBQCAcDq+srNx49y6XC+JSq6urbrcbkOGRSCR3WQEyqfr6ekh3c7vdh4eH09PT8NvZ2dnFxUW32310dASVwCEmd3h4aLfbvV7v6enp0tJSOp1eWVkZHR2F+uoul0ur1UI5NKVSCRBgmCiBQEAikdBotGxNaJCZmRmBQOB2u9VqtdVqtVgsbrf75ORkYWFBq9WOjY05nc7d3V2HwyESicLhcCaTicVi0OLi4mI0Gu3t7QVCIZ/PJxAIZDIZgMwh8szlcm9UUDk7OwuHw3K5XCaTOZ1OSGew2+12u31xcdHpdFZXV3M4nLOzs1AopNFoZDIZDLJSqTSbzTDjp6amIPB5A3aOx+PLy8uFQqHX6z07O9vZ2QEGtMXFRSCQZbPZ09PTs7Ozjx49KiwstNlssBC4XC4+n8/lcj0eTyqVGh8fp9FoULX66OhoZmaGxWL19vbK5XKPx8Nms3MJgi8vLwFNRKVS6XQ6kJ0zmcyFhQW73d7R0QFUk0Cbo1KpWCwW0Ff5fD5g1wSCHbjbycmJTCaTyWR7e3t6vX5hYSEWi0mlUoDZ8/l8tVoNZKEul2t9fR0ColBG/n0TkHwQCp9MJmk02vPnzwFg43Q6LRZLQ0NDTU3NzMzM0NBQcXFxe3t7Xl4eEolsbm6G4jMvX770er0qlUoqlbrd7rt37xYVFeXn55PJ5KmpqdbWVi6XC3jPcDj88uXL0tJSKpXa1tbW0tIyNTU1Pj5eV1cH2FU8Hh+Px2FnTiQSPB5PLpdXVlb29vbabLaioiLgRevt7c19H+vr62w2u7u7OxwO0+n00dHRVCo1ODjY0NCQn59fW1vb0tLS0NCwvLyMxWJfvnzJYrEaGxsnJyfb2tpYLFY0GsXhcEtLSxqNhs/n+3w+LBYLPwSafcC9isVirVbLYDCIRGI4HEahUJ2dnbmjp1ary8vLu7u7v//++4qKisbGxo6ODqfTCQSY8MjT09MdHR1dXV0LCwt+v59EInk8HhQKRafTg8EglIIHUl2pVNre3i6RSHg8HmDXOzs7R0dHswb/6ekpQCEAHM7j8UZGRggEAgaDoVAoUOWeRqMZDAZAzofD4ba2NhqNZjKZvv3224qKCsjPYbPZMLbj4+PZZ7m6uurq6urs7ORyufX19fPz82KxuLm5eWxszGQyQcH527dvE4lEoVDY2NhYU1MzNDSkVqsVCgWTyVQqlUNDQ11dXVKpdHBwkEKhdHR09Pb2ajQaHo83NTVFJpO7urrm5+cxGExuefnLy0sGg9He3k4kEjs7O+12e19f38jISDAYxGKxwOoNsXcKhQLY7eHhYT6fPzAw0NLSAjyWWVPl8vJybGyMTqdvbGwMDAyQSCSFQjE+Pq5UKgGx29TUhEKhhoaGJBIJHo9nMpkymYxCoQwPD/+v4KW3WCz37t375JNPGAwGwELQaDTo6sbGBhqNLiwsZDAYH3/8MUDEaDQalPWASu9isVgkEt26dYtKpTY2NqLR6ImJiaKiIgQC0draKhaLORzOb37zm7q6uoWFBSaT2dDQMD8/z2Awnj17VllZ2d/fT6FQaDQaCoUiEAgSiWRoaCgSiaDRaDweb7VaP/roI4DKYzCYXOeN2+0mEAhOp3NnZ4dKpUokkkgkUlFRQSaTi4qKIMejrKxsYmICAG1Go7GiosLpdBKJRAwGIxaL0Wj08vIyHo+n0Whzc3PPnz9HoVBoNJpCoYRCIYfDgcfje3t7W1paUCiUXq8Ph8NIJHJgYCB39IaGhh48eCCTyb788svGxkYGg1FQUADA4enpaQKBwOVyAVqLx+MdDgeLxZLL5cvLy8AD6fV6+/v7zWYziUSSy+Vms7mgoADQsoWFhTQarb29Xa/XZ7ev7e1tHA6n0+kmJiZ6e3vHx8e7urqA+HV4eFilUvX19bndbovFwmAwotEo0HLTaDRgEFepVPBGQqGQx+MpLy/PEkuen58vLS3BQmA2mwEJj0Qiy8vLLRZLNBplMpkAVlOr1f39/VarFUiyKRRKbW2ty+VSq9VANwpjW1xczGQymUxmdXW1y+UKBoP9/f1A40smkwOBQHYMr66ucDgci8UyGo2NjY0ul6utrU0oFDqdzmfPntHp9I6ODh6PJxKJmpqaIpFIb29vNlXmk08+kcvlN1jD5XI5rAJCobCyslKhUHg8nq6uLrFYXF1d3draOjo6SiQSAUrU398P7yIQCPyvMOmJROKXX35ZVFRUVVWl1+t7e3sfPXrU1tY2Ojq6urqKw+EaGxtVKlVVVRWslzQaTSwWV1ZWfvbZZ0CljMViKRSKxWLBYDBUKtXpdObn5xOJxOXlZYfD8fr162+//ba8vBzw2K9fv15dXW1tbSUSicPDw0gk0m63T05O0mg0PB4PGEk+n19RUQHk2S9fvnQ4HEgkEoVC5XZbIBCUlJR4PB6j0djW1gZpmE+fPtXr9f39/ZDTkpeXh0KhADY3OjoqkUjcbndXVxdkCjQ3NweDQZgBBoPh8ePHNpsNgUA0NDRcXl4mEonnz59Daa07d+7QaDQ0Gt3U1ORwOLJ92NvbIxKJRUVFKpUKWNMZDMbjx4//67/+i8VidXR0IBAIpVLJZDKLi4uBf/7FixcEAqG/v7+urg6Hw9Hp9L6+Pi6XW1VV1dnZ2dHRcevWrenpaTQajcPhzGbzo0ePnE5ntsW1tbVvvvkGi8W2traWlpZ6vd6GhgaNRqNWq0kkUiAQgCyA/4+9N39KNMvSx/+l6YiJmJj5RE93z0xMTNV0V1ZXV3dtWVW5VK5lmqYL7ru4IIIgIqAoIPsmmyAguyyCgCuyibIIiLsC7vr94cQQfs2q6qwlK7Or+/yQYcLLvfe973u3c57zPGNjY9CqtrY2EokE+Wezs7NXV1e9vb1VVVVjY2NIJBL4p6HkXC43NjYG8MfR0VGJRDI2Nnb//v1bt24plcpMJtPS0iISia6urubm5l68eGE0GhkMhlqtHhsbe+edd4aHh4uKihobG+PxuNlsfvLkSX19fTQaFQgEv/rVr4hEYkNDA+ye2tvbYd9euKmDg4Ompqb29naxWNzb2+vxeL766isMBgNE2qAS0draymKx3nvvvYGBgXfffbezs3NmZub999///e9/39/ff4NhenJysrGxUaFQhMPhr7/+GoFAYDCYzz77zGq1Njc3CwSCqamphw8fQvpAeXn5l19+KZPJ/l5ILAUCAYvFslqtxcXFVCqVyWRC/oZKpVpYWIANrUqlMplMQNgslUpHRkbQaPS9e/cAl06j0ZLJpNlsJpFIExMTExMTxcXFFAolFAoplUocDme32+vr6+GEhsFgEokEqBRNTU3V19cX9quZTIbD4XR0dPT29iKRSBaL5XQ6DQZDJpOhUCg3lladTodGo2dnZ2UyGWRZBYNBSJLTaDQikUir1eLxeMCowXkVcvWpVGpHR0d3dzePx/P5fMPDw1DR6OhoOp0eGhqiUqlXV1dra2uPHj2COaKlpaW7u7utrU0oFF4nM06lUoCrVygUcEoHEDjoRjQ3N9PpdIvFgsPhGAzG3NycRqPp7Ozs7u7u6emBTCQWiyWVSs1mMxqNbm1txePxSCRycXFRKpXabDafz9fQ0HB9Mdzc3ITNTk9Pz8DAwNraGovFCgQCTqdTIBBsbGwMDw87HA6bzYbFYiFFRy6XS6VSgUAAXk+RSNTV1YXH49vb22UyWYFvJ5/P6/V6kUhEIBBGR0e3trZCoRAI5hgMhs3NTRaLBd7yQCCAx+PhPBwIBPx+f1VVFRqNLisr4/P5qVRKIBDU1tYCMfnY2NiDBw/a29tramoYDAa8JHq9vuC/PD8/n52dhfMXpLVFIhE4ViwuLo6NjW1ubhKJRODhLi0txWKx1dXVkMdJoVD4fD6VSr0+C5+fn4+PjyORSGBDHBkZaWxshHxbSNleXl5eWFjo7Oy0WCxcLre2tra1tRWe7OuOibwVA35vbw/c0cBCfXZ2trS0ZLfbgcIZ3Kdra2sHBwfBYDAWi2UymeXlZWDzTqVS8O3p6SmAtycnJ+H8/ODBg46ODp1OFwwGj46O5ufn19bW0ul0OBzO5/PhcHhnZyeTySwuLl53xaVSKbvdDrTW4Ec9OTk5OTmJRqM3zld7e3vA1bGzswMu7gJrciaTAc7mg4ODk5OTlZUVn8+XzWYhzgzQ3c3NzXw+f3x8DDTMuVzu4ODg/PwcnNKBQACWTZiMwGm/ubl5gxYin8+D53J7ext8wgA+2dzc3N7e3tjYgDILdMgnJydbW1sbGxtw2eHh4d7eHnB1xGIxCAHs7+9DY46Pj6Go63EB6Of9/f18Pg/O/J2dnaOjIygNpKzz+TxUurOzA7EG4PyAErLZLOAOdnZ24MpC4efn5/BAIdAA8bONjQ1QGYTOhMuA3Bpw+9BIgAblcjm73V5XV0en02tqalAoVDgczmazuVwuk8nA9dclHK+urjKZDJFIJJFIXq8XnOpwDSC14cqzszP45PT/DL6FfwtxmcvLy4ODA8j5U6vVsGIXfgUhGzjqX15e5vN5t9uNQqHYbDafz6+rq/N4PK8b3vNWDPiX7fz8HB55wRECHVF4TjeIIuFD+ESj0YA+WXt7O+i9wecFssTCxfBoXw7GFt7vl6t4FXtZHxZel1e9+asrh8PR3NwsFAq3tra+u963FsL5g+3V7+jbrpyZmamuru7v7+/u7pbJZH91CPn9/mfPntHp9B8PGQYJChKJJJPJXqW0ZDI5NDTU39/PZDKZTObPAHN6Swf8j7F0Og2KoqBb8Lc4JEDdIR6P/y02/o3b3t7e0tIScIq+ChRvb2/P5XK9rNv7A+zi4mJnZ2dpaQlSrf+qgXyg3+9fXV39eUCNv4QB/+PXhJ/n52+VFe7l57mpn7aW66X9kh7Kz2B/MwP+6OhobW0NgFMAv4OT/Pddw1OpFAQ/Xt7Mw0E9HA5f336fnJwAsgpOdz/Z/bwF5vP5XpFQCYgoV1dX5+fnYYd8dHT0VwNIh4eHoVDoBlDv8vJydXV1aWnpBtJxe3t7dnb21bmfs9ksCEj9wh7K67a3ZcAfHx+D9+jbLlhfXwf9pmQyCRsnEJOGSM/LdnZ2ls/nX85Xkcvl9fX129vbgEW9/tXBwQGbze7v77/++fb2tkwmYzKZkUjkx93i1dW3rKt/NW3zZafAjTK/45gKbqdvbEZDQwMGg7m65s74xlqAfGJ3d3d4eLiurg5mw2g0WghrFWq/UdHy8nJnZ6dEIgHapsK3AEO4kVRvt9uLi4uvgwhveD1u9Nji4uKXX345MTFR+KpwQcErdr1bbvTDy31ydnYGb8sPy6L9W7G3ZcA7nU4gli141ApvIbhAI5EIGo222WyZTAawtCqVisfjFXSFYMWGXwHEdXp6+vqKAXmOEGgFV39BWQl+m0wmgTDv8PAQHLAANR8dHdXr9Xt7e9eruG6FD09OTra3t0FG5uzsLJvNgpMcLsvn86lU6jroumAHBwfpdBpo5HO5XDabLRw+wZ+fy+Xi8fje3l4mkwHkfKGRQNezs7MD7vetrS2IDgBFdCQSiUaj18MQQM+QSCQ6OztpNBoQTm9ubkKuCMhvgjYuQPqBLSedTrPZ7L6+PogIgIDn1dUVMGptbm4C+XcBKH5xcTE3N9fY2Dg3Nweu+7W1NUgyJZPJNBoNNCoLDXM6nZWVlT6fD3oym81Go9HNzc3z8/N8Pr++vg6ilOfn59lsdm1tbWJioqioyGKxFOILe3t75+fngFGHrIFQKLS+vn54eLi+vn5wcBCNRiFkEIvFtra2UqkUpDDu7u7C5m5hYSEej383Pf7fur0VA35/f7+vr+/evXvT09Nra2sGg4HBYIyPjweDQTwe/8UXX3A4nIWFBRQKBUFsOp2+traGRCKrq6tra2s1Gs3R0ZHFYgF6I6FQaDKZysvLVSoVeErz+bzX61WpVBAOFQgE9fX109PT8LZls1kAitTV1Q0MDPh8PoA6Nzc3j42Nrays9PT0ABR8cnKSw+F0dXXBHzQaTaFQ9PX1sdlsAHs6HA48Hg8wrLGxMYVCwWQyg8Ggw+Hg8XgqlYrD4dTX12u12hs9MDc3h8fjUSjU06dPOzo6MBgMjUbLZDJTU1PAeQacjX19fZWVlUgkcnR0FGBFBoMBAul9fX0ymYzFYvX19Q0ODrLZbMiBAwJpqVQKy+za2hpA04lEIoSOQENSJBLNzc3JZLKqqqqenh4MBlNfXz82NjYzM0On02dnZ91uN0CA8Xi8QCDo6OhQq9UgmK3RaLBYrFKpjEQi4Btvbm4GOq3W1lbAPonFYjKZXFlZGY/HhUIhAoHo6urq6+srYAqA8LOyslIikRgMBolEotFo2Gy2zWYzGo1EInFgYIDH46nVao1GQ6PRurq64L6ATxKNRtvtdp1ONz4+DsA7j8dDoVCqq6sbGxvr6+uDwSCVSm1oaOjq6qqtrZ2ZmRkcHNTpdIlEYmBgAIjPAdfodrvfoBTU67a3YsAHg0EsFovBYLxeb2dnZ1FRUUtLC4fDcTqdt27devfddw0Gg8fjwePxoVCovb0djUavrq6WlpaSSKSHDx82NDT4fD4ajTY5OYlAIDo7O3U63b179+x2O5S/urpKp9MnJycfPnyIRCJdLlfh29PTU5/PB98+f/68rq4OoBoWi+XZs2c4HC4ajaLRaIBtyuVyLpf7/vvvSyQSBAIBzM3/8R//gcPh6uvrm5qaBgcHP/roIywW29jYSCQSFQoFAoEA7mpAfU9OTn766acMBuNGD0ilUgCH/Pa3v62oqGhra3v06BHQdVZVVdlsNpvN9sknn2AwmD/84Q8ff/zx4ODgw4cPKRTKxMSEwWAAhYbOzk6AcBCJRCQSSSaTgUizrKxMpVJBhrnJZALdyKKiIuDzf/bsGZlM1mq1NpsNjUZ/9tlnZWVlpaWlf/nLXygUCgBylpeXITFhYGBgbGzMaDR2dnZSqVSXyyUWi2dnZ5ubm/v7++Vy+UcffYTH4ysqKkZGRubn5wkEglarhSmYwWC89957BoMBhUKVlpb29PSUlpZGo9Grq6v9/f3+/v7f/va39fX1BoMBGKMBYUUikfh8vkgkampqAvZ4qVTK5/MBTTwyMiKXy4FllMfjMZlMo9HI5/M//vhjvV7/6NGjr776qqGh4X/+539sNtuDBw8KHJVut7uhoaGvr29hYaG2thbgtAQCobi4OBwO/2OFf702Pj6Ow+GcTqfZbP73f//3zz77TK/X2+12pVIJYgP5fB7kKJaXl+l0Oo1Gm5mZweFwoVBoZGTk6dOnNBoNJoju7m4CgWCxWNrb2wHtmE6nBQIBQK9ra2t7e3uXlpY6Ozvh29XVVZCyMJlMbW1td+7cIZPJTqfT6/Xi8Xg6nW6323E43NDQ0PDwMJAifv755y6Xq6Ojo7a2ViaTffrpp0wmk8FgNDQ0tLe3o1AonU4HQOtgMFhUVATg//b2djabDbzOcPK8bqOjo0VFRWazubq6mkwmC4XCJ0+e3LlzBxJ4AoGAzWa7e/fu+Ph4Q0MDINKrqqr+8pe/SCQSANINDQ0hEAhYrAC4zmazGQxGX1+fWCyGnU40Gh0aGiKRSHK5/I9//GNXVxeBQPjwww/7+/szmQyPxwOAY2trq0KhqK6uplKpAGJZWVmhUCj//M//XF1dHYvF3G63UCjE4XC9vb2Q0kelUjEYDBaLbW1ttdvtsOSKxWIqlQr4tunpaTqdXllZicPhmpqa2Gy2Wq3GYDAAK7Lb7X/605/+3//7f1wud3Z2tqGh4datWyQSaXl5uaqqCovFajSap0+fslgsYNen0+n//d//PTIygsViORwOj8e7detWV1cXIG3pdPqjR4+oVGpFRQVQjP7v//7v4ODgixcvyGSyRqOpra1dW1vr7e198eIFEBMXFxdPTEx0dnaWlJQAvOeXwW/zsr0VA55Op3d1dfl8Pq1W++c//xmyXGDGNRqNl5eXgHzkcDhAFAEjh8fj6fV6mUzW1dUF6GgUClVWVtbf3w/5W0BCNjc3h0KhcDhcX1/fkydP+vr6YISA08jj8fT29gIr85MnT7788suGhgaNRtPV1dXa2kqj0YaGhnA4HADvh4aGysvLHz16ZDabR0dHe3t7Jycn6XQ6hULhcDjt7e0YDAYyT/v7+yG++sknnzQ3N5PJZBwO19/fj0QiEQiESqXa3d0tJHKfn59LJJL29nYAhwOwFIfDvXjxAijNPR4PZLOAEAJovAwODn711VcdHR319fVwfmlqanI6nSaTqbGx0eFwTE1NtbS04PH4aDQKS9bMzExXV1dNTU1VVdV7772Hw+GoVGpJSQmPx0ulUt3d3TQaze1219fXh0IhDAYDLPfPnz9fWFiQy+VPnz5FoVBjY2MEAkEulwOUjUQiDQwMUCiUrq4uyLcdHx9nMBi9vb04HI7FYpWXl/f29uLx+JqaGjQaXVVVpdfrp6ene3t7ORwO4FvHxsaKi4uHhoY6OjpoNFpnZ+fDhw8ZDIbb7S4vLy8uLm5sbHzvvffodHpLS0tJSUl5efnHH39MIBAAD1tbWwv9jMPhWlpaSktLv/7668bGRrlcbrVaQa6jsbFRIpHMzMyAJ2Jra6u/v//u3buQl/r111+3trbCFm91dfVl/p9fjL0VA97hcExOTgISUywW9/X1ARBCoVDACrC8vMzhcCCVfXJycn5+fmVlBXT5lpeX0+k0qHYoFAqVSqXVaqemptRqNYC0Dw4OIK9LoVCIRCLIW9Lr9RAW2t3d1Wg0/f39kMAMZNIcDkcmk4F2lVKpVKvVer2eTqdzuVyDwSAUCqenp2dnZw0Gg9PpBKZkl8ul1+tNJlMul3M4HCaTKZ/Pz83NlZeXOxwOkBzlcDjT09NTU1MKhUKtVgeDQRiHe3t7wWAQ8ihCodDs7Czow3m9XpFI5HK5QKkqEAgsLS1Fo9FAIDA7Owt01zqdTqvVulyudDptqNWp4gAAIABJREFUt9vB6waUz0NDQ8+fP3/48OHAwAC4AHO5nMlkEovFXq9Xo9GEw2GfzweZ59lsFpLwgQh8f3/f6XSCaqLJZEokEsByPTc3Nz8/r9frV1ZWQGpufHzc6XQCFHp5efn4+Hhpacnn87lcLrPZHAqFXC6XSqWanJz0er3T09NCoRC8cQ6HY3V1FfyXCwsLer1+dXV1cnIyGAx6PB5Y6iGfHLLo5XL56uoqiIh5PB5ApGs0Go1G43a7DQbD3NzcxMTE5OTkwsIC9Ay4MCF1z2g0gkNxbm5ucXFxb2+PRqPR6XTwJorFYpvNNj09DVTfmUzmdWetvSl7KwY8ILfh78PDQ/CyAkYdXohcLrexsbG3t7e7u7u7uwvEKZubmyDteHV1tbe3BxTi2Wx2b28PHMUFZ/jh4eHKysrOzg58fnBwAM5z+HZvby8cDh8eHkIz9vb21tbW9vb2jo6O9vb2ABKfzWbj8XgymTw5OYFmHB0dwcWXl5e5XA44GMBzfnh4CAmYFAqlIC2wu7ubTCbPzs6AYCscDhdojAs8MICTB2YYaBs47UFKHUDj4Jk/OjqCK8GRDuXARhSYuZeXl8GjWV5e3tLSUkhQyeVyMPihc87OznZ3d6GE4+NjqOXk5OTi4uL4+BjimicnJwUo+NnZWQEzf3V1lc/nt7e3j4+P4XPAih8dHcF/gQDn4uICogZX/8dcWCi/cFQGCqCLiwvIPj47OwN8PvwESJCgTwDnf3V1BSG0g4MDwGVA1Xt7ewUWM/gDIBvQY1DXwcHB1NQU0CUUuOhARvLi4gKyG6CFr+FNf/P2Vgz4X56Fw2E+n6/X69/UewNJRA6Hw+l0Op3ONyI+/3YaKNgymczrjDd/P/aPAf9a7FVSZV4fuuMXjBv5ae3vsKN+IQMe4Bk3cHVAewjb1FcpobA/vP758fHxT0gFD6Ag2Ov+mHIgW/ZNhYsLsJyrqyvYnBf20jcMMJGwjf9eVZydncGJ6RUf39tscMwBN+0bd/7/Qgb83t6e1Wp1Op2Fw+rJyYndbn91eaDDw0PgTrr+4eXl5dLSEpfLfcXkp79qQG9otVp/pE/I4/E0NTUB1u27q3sdzqdUKsXhcPR6/dX/EbPz+fxvFMACQh5Q7/teVWxsbIDA7is+vrfcPB4PnU6fmpp642erX8iA393dBfV4oII+Ozubmpp68ODB6OjoK77xZ2dnQ0NDo6OjNz6H2P7L1IKxWAxAI9/LDg4OCASCyWT6tjb4/f5XGRtut7ukpOSvpr4kk8mX01F2d3evU6y+it1YY2Ox2MjIyPj4+PHx8c7OjtVqhXDJyz/c2toCLpe/ukrfuCASiRAIBIPB8BPuYn7wTuHGKH11v0xhPVepVFgstkCDBa5EaA+ICAPy+h/psa9q29vbBALh1q1bUqn06uoqFot1dna+//77Wq12a2tLoVBIpVKXy7W6uhoIBNxu99LS0tHRkd/vl8vlU1NT4XB4bW1NKBSazea9vT2DwTAxMTEzMxMKhYxGY29vLyi0FhgsDw4OSCSSSCS6vLxcWFiwWCzRaDQSidhsNtCcMBgMfr/f7/cvLCxsbW2Fw2GdTuf3+zc3N0tKShoaGux2O7REqVSmUqmdnR2gtW5oaCjsMk5PT10ul1Ao9Pv9JycnbrfbaDTOzs7G43GHw0GhUNbX1+fn58fHxx0Oh8vl0mg0Xq/X5XLpdLpQKAQ0VQKBABgggT5ocXGRxWKB4Pni4iKI3hqNRqlUOj8/v7W1BTw/MzMzer0e2FQLm+qdnZ3Z2VmTyUQkEvl8Pgizp9NpwMMQiUQgbAEWJwaDMTk5mUqlBgYGRkZGJBKJzWYDgP3ExATo7cbj8enpablcHggECu/6wsIC4IXr6+sjkUgwGOTxeFNTU/F4XCqVSqVSwEEeHByYzWaDwSAWiyGma7FYJiYmxGIxqN+CcPj4+HhBQ+Li4sJsNg8MDIB6vEAgkEgkbrd7fX0dCHZBDXZsbIzH442NjYVCoUQioVKp5HL5+Pi4x+OZn5+Xy+USiWRiYgKg0yDju7u763Q6ZTKZyWQaGhpaWlqCuKNCoQABXJVK1d3dbTQaDQbD0tKS2+0G7LDD4WCz2VDUyMhIIVL7+uwXMuDT6XRLS8utW7f0en0ul+NwODU1NcBPrNVqgbCRTCaz2ezh4WE+nz81NQVcyz09PT09PRMTEwD/XFpagpA7CoWi0Wijo6OAbCkuLh4eHob8sMvLS5/PV1FRgcPhfD5fb29vUVERxMMrKir6+/vJZDIKhaJQKBDDl8lkZDIZFjqfz1dZWVlSUkIgEBgMhkgkqqys1Ov1LpcLKFPv3r0LPI1XV1eHh4c1NTXPnz8H4efa2tqysjJAtorFYrPZbLVaRSIR1EgikQAYQyAQurq6lEqlQCAA6siBgQEAzIO2cWlpKUxhHR0dCASio6MDiJOhATqdTiQSAddtUVHR48ePYS9wfn4OEDoArgLwpr6+PpVKdXZ2VldXFxcXt7e3r6+vj42NMRiMoqKi8vLyhYWFysrKtrY2BAKBQCCWlpaASLOsrAyBQNjtdgQC0djYCCmPZ2dnwDkJuJ2SkhKJRDIwMHD79u3+/v7p6enf//73ZWVlNTU1zc3NS0tLgHQqKysrLi62WCyjo6NDQ0OVlZUPHz7EYDAIBAKA9EKhsDCK6uvrf/WrX1VXV3/wwQefffYZIIJJJFJraysCgRgaGurt7f3ggw9qamrKysrweLxCoejp6ampqYG6yGQykUh88uRJV1dXfX19XV2dSCTq6+vz+/04HO7Pf/4zIBeFQiG0Z3R09IMPPlCr1TQa7U9/+hOFQuHxeCwWSywWEwiEhoYGkUj08OHD58+fAyOb1Wr9O6W4+l52cXERjUb7+vq+/PJLJpPpcDhQKFR9fT0Q4DIYjFgsRqPRJBKJWCzu6ekRiUTxeLyvrw+gMlgsFlB9NptNr9fjcLjV1VUmkymTyUgk0p///GdgyJNKpbDZPjk5KdCe4/F44GD1eDwTExNffvmlQCBIJpMmkwlAaaFQCIFAAOsucLZDtIzL5Q4PDxuNRjKZDIMfqKxHRkZ8Ph/cVDKZrKqqotFoPp9vZGSkpKQEXnStVksmk4FPHpTJgVOpqKios7OTwWAAIlgoFMJWhcvlTkxM1NfX2+328fHx1tbWhYWFgYEBwMlB3ggI1ONwuOHhYTQazefzoRPa29thQ7uyssLn82UymdVqLSkpMRgMcrm8u7s7FAoRCASn0ymVSp8/fy6VSmFeYzAYdXV1CoXi008/pdPpYrH43r17KBTKbrcD7yXgo7/++uuxsTHYt+/s7JBIJJVK5fF42Gx2V1fX3bt3gZZbJpOZzebbt2/DetjX1+f1eoGHU6VSdXR0IJHIhYUFl8vFYDB6enrq6ura2tqoVCqk38CAz2az7e3tX375JY/He/r0aWVlpVarHRwcvHXrVnNz8/j4uEQiaWpqqqysVKvVQDTK4/HEYjGRSLRYLHQ6HYfDQcYBbEx6e3sVCsX9+/enpqaoVOqTJ0/0ev2LFy/6+vpAzMftdpeVlY2Pj7e1tf3Lv/wL5IMCz6pWq62qqpqfn6+qqurq6pLL5XV1dYXUz9dnv4QBH4/HTSYTCEv85S9/odFo4+Pjn332mVqtJpFIVCrV4/GUlpZOTk7u7Oz09/eXl5e7XC4MBiOTyQYGBp49exYOh7FYrEAg4HK5nZ2dXq/30aNHPB5PoVDU1ta63e7q6mqhUAiz7/7+fnd398TEhEwmKykpkUqloKDM5/OfPHkCWCB4d5FI5MrKyp07d3p6era2tuRyeVtb29LSkk6n43A4Go2GSCQyGIw7d+7U1taaTCYSiWQymeDgcHh4CPtMgNl2dnZSKBSRSLSzs6NUKjs7O2dnZ0tKSgAo+ujRo5mZmYaGBq1WOz4+3tPTs7q6isPhHA6H2WyGF/fBgweTk5NarRaNRvv9fpBSgT1OMpmMx+MIBAKSi4qLiyHhp6mpqUA1K5FIhoaG+Hw+AoGoqKiQSqVcLpdAIExOTgLjsFKpRCAQ9fX1wJxbX19fU1PT39/PZrMnJydFItHjx48/+ugjq9UKmwur1WqxWHp6esRi8ebm5tXVVTqdfv78OZ/Pp9FopaWldDr9gw8+6O3t9Xq9ILkDuTEcDkehUEQiEQQC0dDQsLKyotfrnz59ajQae3p6AF1fXV09MzMDsF8o/OrqSq/XUygUIpFIJBLHx8e7uroUCoVQKPzP//xPJpMZCATIZDIWi3W73bBZAIxgXV2dTCbLZrMwtXV3d1ut1pOTEw6Hc/fuXSQS+cc//hHmBVCzefz48ePHj4eGhphMJhaLLS8v7+npgSRLAPPX1tZSKJS+vr47d+5MTU0NDw+bTKapqamKioqfhGbru+2XMOBVKlVDQwPIJIEwyODg4Pvvvw9iQ9XV1QQC4dmzZwqFYmpqCoVCwWmzqampu7sbiUTW1dXNz893dHRAtsnXX39NpVIfP34sEolAv2lrawuBQAiFQqju4OAAh8OBhBMOh2tvb9dqtclkcmJigs1mHx8fx+NxOEeAIFl7e/uzZ8/gvAAZtYBmBQ7mgYGBuro6MplsNBpJJFJBwGRzc1Mmk4lEIgCWymQyLBYrl8tzuZzVaqVSqbCNpFAoIIQ0Pz+vUqnS6bTFYhkZGdnY2Ghra7NardPT00BuDYT2BoNhYGBgZWWFRqP5/X5Y2CH/vKqqqr29fXZ2lkKhwPaVzWYXGOlnZmb6+/vhczgGKxSKiYkJh8NBp9NJJNLU1NTs7OzIyEh3dzeJRGIwGFgstr+/PxaLzczMiEQiBoMBcHfoar1e39fXh8fjHQ4HnBp2d3exWGxPT09/fz/k2wwODra0tCgUCpvNJhAIYrHY0tLS+Pi4Xq+XSCR379796KOPQC4CCPaxWCwceVgs1s7ODp/P5/P5BT4MpVI5NTXl9XoZDEY8HufxeBqNZmlpqbm5mUKhgAKKRqPZ39/n8/larXZubg6Hw3388cc1NTXBYBAUBD777DMUChWPx5VKZVNTk0gkQqFQ4AGJRqMgK8Ln88ViMfg1IXV6bm7O5/MNDg7CpCMQCJRKZW9vL8hjAE4UZvPXPVj+5gf85eXl/Py8VCrd3NxMJpOHh4cHBwdGo3FsbCwej8/PzysUCr1ebzab/X6/y+WyWCxAF6HX6/V6PWjCJRKJqakpv9+/uLgokUimpqYsFks4HN7c3ARwq8lkKjiWTk9P5+fnwRsXDAblcrnH40mn04lEIp1On5+fZzKZ6elpiBGenp4uLi6KRCK32w083ODmAeQpCNHNz8+DZt78/Pzm5maBAQK0WcBxsLm5aTKZlpeXgdsrFArt7e35/X6v1zs3NwcJBSCHGggEJBKJWq0eGRkJBAIbGxtOpxMg+gBGnpubOzg4ACRyJpNxu90mkwnce+Bpj8ViarV6bm4OsOjQz/l8fmZmxmw2p9PpYDAIfOEbGxvb29ter9disUA4IJFIaLXahYWFdDo9Pz8/NzcHspOhUCiVSi0vL8MZJJlMBoNBnU7ncDgKVB9nZ2eBQMBsNoP7EFjAdTodyHVGo1Hg8E4kEqAshEajW1paQBjH7/e73W6fzwdqjYlE4vj4eHV1tRBJubi4iMViu7u7uVwuHA4DY1oikcjn84FAwG63b21tHRwcACf36upqIpFgMBiwPj948GBkZIRGozU0NCCRyC+++EKn06VSKZ/Pt729vbKyEo1GARa9v78PPB9ra2ugfZhOp/1+PwhgglZkJBKJxWJ7e3urq6tbW1twnIFd4d+LEMWPsZ8TlfGz8T3+mIp2d3dNJhNQhrxKSHJra4vJZI6MjLxuVbPvsO97v8vLyygUquAT/W6Q7A0CrFe04+NjyMYHrQi5XM7n84VCodVqpdFo30as9vbb3/yA/4fdsOPjY1DmeEWMx9HRUSqV+tvKBj0/P4/H45Bmu729/Zom4mw2u7S0BERpABkMh8NAo/q3m1rzjwH/NtqNRf57rfkFjr1Xv/57t+/72OvjhMxmsze2MN9W0Q/uT4BsF/4LRJff/ZO3nAPzHwP+zRhgYG7QS4KFQiGn01kA856fn4OS7M+DnP++LysstvPz89+IgT05OQHp+NeNkD09PQ0Gg6AMf+Or9fV1uVw+NzdX2PIkk0mxWBwOh79vLfF4HJTqv7GXTk5OgsGgWq1+g4ejv2pvxYD/yWfEQoGFPwr0MtcNdrMFv9TPaaFQSCAQuN3ufD4PCfaFr6RSKZ1OTyaThdxvtVpNJBJf97oRjUZjsdj3reX09NTr9fJ4PI/HU/iwUMj5+blWq+VwON+NAv7xt3Z6eqrVahUKxdra2v7+PsjRwVeBQADYhHZ3d/f39y8uLtbW1ioqKq7rw7+izczMdHR0fFvw7ODgAJB213VpX9F+tk3BWzHgr66uDg8P/X5/OBwG1+XV1dXFxcX6+jpwTuzu7sJiCHZ1dXV2dhYKhcLhMLBWg7s4HA6DHOL1Ab+3t+d2u9VqNQgPgQTF0dERKBkYDAYgbwHGYkA1X11dJRKJ5eXleDy+vb29t7eXSqXW1tZe1q46Pz/f3t6GtWVtbQ2+2tzcDIVCmUwmn89vbm7u7u5CUAcmnUwmk0gkpFJpT0/P7OzszMzMzMwM8Dqvra1FIpGOjg4ymRyNRnU63fr6ej6f12q1OBzO5XIdHBwcHR2tr68vLy+HQqGjo6NYLAYc0oFA4AY8Pp/PZzKZcDjs9/vX19eBRSMWi83Pz/v9ftBXTCQSwNi9sbEB6u6FvgVZiKOjo3Q6DfcIwQXoHI/H4/V60+l0LpfTaDRCofBGJs/R0VEymZybmxsYGJDL5aDzGQqFlpeXgeg6EolkMhlAoV7v0pOTk0gk4nQ6FxYWIpEIsINAO7e3tzOZDOiCzM7OrqysANNGIpGYnZ1Fo9ETExMej0en0wG7WSqV8vv9YrG4vLwcNOcdDgfg+UDCMRQK5fP5g4OD+fl5h8MBWqOAqAVinAIvCxgwC0okkkQiAUenVCoFrD7JZDKVSvH5fBaLpdPpIpHIxcXF0dFROBxeXFwMBALAUA7e+93dXWDXXlxcBKbmv68BD/xKbDZbKpViMJjJyUmImmg0momJiVQqZTabqVTq3t7e4uJiPB4/OTnx+XwsFotEImk0GrPZLBQKeTweMEbfUIxwOp1NTU0gYqHRaObn59fX1yORSDKZHBwc5HK54XB4eHgYgltLS0vZbDYWi0ml0oGBATabbTab7Xb70NAQqDiLRKLrzrBcLjc1NdXV1dXQ0ECj0YA7SafTdXZ2jo+PAxJbIBCg0eju7m7wMAHKFYVC1dTUBAIB4IE8PT1dW1sDgDpgTjweDwqFikQii4uLPB5vcHAQjUbDxKFUKoeGhrq6uhKJBJVKRSKRQqGwvb39RjJPMpmk0+nt7e04HI5Op29ubgYCgbGxMSB+g0FFpVKBo8poNCKRSLlcfnR0ZLfb6XQ6gM/C4TCPx+Nyub29vSQSyefzZTIZmUyGw+EaGhr4fP7GxsbAwIBOp7v+ygLJBGBs7969q1ar19fXlUoll8ttbm72+Xw6na65uVkikdTU1ExNTV1v9uHhYX9//7179wgEQk9Pj8/ni0ajgGkF6e6hoSE0Gt3e3t7f37+6urq8vCwWi5lM5hdffDE5OSmXy7FYLLAVqVQq4PZ88OABxOo5HE4+n5+cnMTj8bW1tUKhMBKJmEwmAoHw5MkTJpNpMBhaW1uB6Lqjo6OAw7+6ujo7O1OpVL/+9a+Bby8ej6fTablcLhKJnj59OjY2trS0VFlZOTAwUFxcPDIyAuz9ALnBYrEGg8HtdgMFeDAYjMfjLBaLQqF89dVXVCr172vAg756Op1eW1srKioSCoXBYJDJZEKaAWASuru74/H48PCw3W73er1DQ0OLi4tA8GoymTo6OkpLS/F4PJlMvpGLplar29ra/H7/2NgYhUKh0+lsNntubi6Xyw0PDzOZTI/HU15eDuhIFosViURwOByAUoeHh1UqlVgsLioqIpPJFAqlo6Pj+qy/t7cHmC2hUAjYcqFQKBQKm5ubxWIxwDCeP3+OxWJZLBaTyRwfH5dKpYDlIhKJkOQD/LZMJtNqtWo0GhwOZ7FY/H4/Ho+PxWIymezp06c4HM5sNi8tLQkEgqmpKZC1X1lZQaPRjx49IpFIDQ0Nq6ur128cOrOsrEwgECCRSGCzMxqNZrO5trY2HA5zOJympiaAIVgsFhhRTqezoqICsP00Gs1ut7e3t5eWlvb398tkMkDC6/X6UCg0PDxMJpNjsVhXV5fRaLxeNUzHMJXU1tYyGAyVSqVSqRYXF+vq6lwuF5vN/vDDDykUSlVVVYFNHCybzfb09NTX13s8HgQCMTo6OjExUVFRAYhgtVr96NGjsrIyiURCIpG4XK5YLFar1VartaGhwePxqFSq/v7+VCrFYDC0Wi1gnEdGRpLJJB6PFwqFiUQCSC+HhoaSyeTU1BQAdTEYjEgkcjgcwBdOIBBoNNrCwkJhKIbDYS6XS6VSFQoFgUDg8/kA9wiFQg0NDfAevv/++xQKBYFA8Pl8t9vd1dUFibEDAwN+v39qaurrr7+G/Y5cLmexWLOzszU1NUNDQz/tgPoOe/MD/vT0tLu7G4/H53I5oVB4+/btyclJk8lUX1+/t7cHO66pqSk0Gg1ruFqtBsDpxsYGZC8Yjcby8nIWizUwMMDhcG689yApkclk6HT66OgoCoUqLi6Ox+O7u7sjIyMajWZhYaGoqIjH43V0dAwNDcE7GgqFqFQqPDAsFtvb28vn8+l0ukwmu77CRyIRoHa1Wq2jo6PNzc137tzp6OgA0Nv8/HxRURGVSh0dHRWLxSKRqKamBhgaq6urTSbT2tpaW1ub3W4HBvvZ2dmqqioikRiJRHQ6HZfL3d7eHhwc/M1vfgMAWAaDwWKxnE4nk8nEYDChUKi7uxuDwUB3XfdC5fN5qVTa0dExOjoKiHGYg+bm5uh0OhKJjEQiq6uraDR6cHAwnU5D7sDGxoZCoWhsbNzY2BgcHBwcHHQ4HE+ePKHT6cPDw0qlUqFQlJeXLy0tTU5OotFotVrt8XhAvKFQ9eXlJQqFGhgYmJ2dRaFQ3d3dpaWlNBotHA6LxeKmpibAAtbW1trtdoADXv+ty+UaGhrSarWQLNDY2Aikwy6XCwRLIOeERqOBahh0SGNjI6DlpFIph8NZW1urq6vTarUDAwP379/3+/2xWGxoaAhyBG/duvXb3/5WpVIFAoGhoSEGg+FwOKqqqsRiscPh+OKLL4DXlMFgXJ/cx8fHyWRyKBQSiUTDw8NdXV04HA5AkE1NTZCRWVRU5HA4WlpaiETixMREc3Oz2+2urKzs6+s7PT212WwvXryYnJyERUKv14vF4pqamvHx8dcwsL7Z3vyAPz4+rq2tvXv3rkAgaGxsLCsr8/l8CoXi3XffHR4eDofD+/v7Uqn00aNHdXV1aDQaSOxfvHjBZrN/97vfsVgso9FYW1sbCATKysrIZPKNAyGZTH7x4kUwGEQgEC0tLS9evPjwww/9fr/FYuHxeNFo1Gq1/td//VdxcfGDBw+IRKJer799+zaFQrl//35nZ6ff76+rq4N0l56enlAodL18t9v93nvvDQwMMBgMpVJptVrv3r374YcfjoyM7OzsuFwuuB0SiYTH4/V6/aeffgoDoKamBoCukPXB5XJ///vfYzCYv/zlL6Ojo7Ozs5DWkkgkOBzOkydP0Gi0SCRqbm5ubGxEo9GwagEHu9PpnJ2dvZF6sbOz097erlKpbDYbkUgUCARNTU1Ato1EIuHc5HA4Ojo6CARCLBZDIBACgeD8/Bwo/cVi8fDwMFDiIRCIQCDQ19dHoVBMJtPt27cLFNpOp5PL5dbX1xcQuGDNzc3l5eVkMhkSZkpKSurq6oaHh1taWjAYDJfL5XA4Op3O7XZXVFQAkQbY5eXl0NBQS0sLnG5MJpNCoXj+/PnXX389MzNzcnLS09PD5/N9Pl9bW5vD4cBgMEDF/fjxY4lEMj09DeTF0Wj06dOnbW1tRUVFRUVFyWQStjAzMzMul+vhw4fPnj0jkUgCgYBAILS3t1OpVAQCwWaztVptd3d3KpVqampCoVDXnzUI7IDIz/T0tFKprKurw2KxaDQah8OJxWLI3oUXBjIUnz9/zmAw7t+/T6VSk8kkgUCoq6ubnp4GMHh/f39vb293dzcoC9lstkL+9euzNz/gz87OBAJBS0sLl8tVq9WTk5MgJFpbW4vFYj0ez9bW1sTEBGS5yWSyubk5iUTS2Ng4OjpaXV0NXMgTExOZTIZIJMrl8uuF5/P58fFxJpOZSCQGBwfJZDKVSqVQKH6/v7e3VyqVnp+fe71eBAKBxWKxWKxarYa8S4B5m0ymWCwGkHjIRb3OJ3F2dmY2mz/44AMUCqVQKFZXV6E6YGhfW1sDx9v29rZSqZRKpYFAgEQitbe3w1Z5eXnZbrer1epMJuPxeNra2ohEIpfLXVxcXFxchOR28M9ZrVbIIVcqlSQSiUgkGo3G6elpk8kEXoNAICCXy69HpLLZrFQqjUQiQKfpdDptNhuFQqFSqQaDAbDGcrlcIBD4fL6dnR0GgwFHoWQyyeVyoRngP9PpdDs7O8APvby8TCKRsFgshUIxGo2hUAgSFm5g3ex2O5FIJJFIsN9Wq9WQWQjpDDqdzuv1bmxseL1eOp1+gzmju7u7qqpKKpVOTEwAgSzk2wPzt91uX1paWl9fHx8fj0ajHo8HtLQmJyeBvXtiYmJpaWl7e5tKpUK